GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 644420315 species occurrences available in GBIF matching the query: All data. The dataset includes 644420315 records from 13637 constituent datasets: 14165 records from NYSM Mammals. 2034 records from Herbarium of Namur. 125 records from Artenbestimmung. 3106 records from Collection Cnidaria fossil SMF. 8587 records from HSU Wildlife Birds. 54358 records from NRM-Fishes. 41 records from Liether Park (LMS), 6c. 349178 records from AMNH Herpetology Collections. 104 records from Schulwald Sprendlingen. 827 records from Schatzinsel Norderney. 2749 records from Miscellaneous Vascular Plants. 3362 records from Plant (NSMK-PL). 105 records from BIRDRACE coesfelder_vogelkundler. 1770 records from Schmidt Museum of Natural History_Birds. 46 records from An der Ohm, (Wettsaasen). 7076556 records from Great Backyard Bird Count. 3 records from Acari fossil - SMNG. 508 records from Guyane_Cacaoyer. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 8857 records from Artròpodes d'Andorra. 3 records from Nannofossil abundance of Hole 94-609A. 2805 records from Fundación Miguel Lillo - Colección Mamíferos. 1 records from Oribates calcaratus. 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 1 records from Waldtag in und um Seelingstädt. 95 records from BIRDRACE BiBi. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 158 records from Total living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >30 µm. 126 records from Total foraminifera counts from M35/1_MSN1050. 138 records from Total foraminifera counts of multinet M10/2_MSN297. 156 records from Dinoflagellate cysts of mooring MST-9 (station 915) with cell content. 13 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 2494 records from Colección de peces dulceacuícolas de Costa Rica. 17618 records from BioGIS - Mammals - INPA database. 3 records from A new species of Lyssomanes Hentz, 1845 from Brazil (Araneae: Salticidae). 71 records from (Data S1) Palynology of ODP Site 113-696. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 70432 records from National Bat Database of Ireland. 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 75655 records from Ibaraki Nature Museum, Vascular Plants collection. 313949 records from United States National Plant Germplasm System Collection. 48 records from Occurrence of mammalia relicts at site Falkensteinhöhle. 1 records from Occurrence of mammalia relicts at site Kleine Feldhofer Grotte. 164 records from Planktic foraminifera abundance of Hole 22-215. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 13 records from FND "Weißer Berg" Leißling. 131 records from (Table 3) Occurrence of benthic foraminifera in the Ledyanaya section. 2427 records from Ibaraki Nature Museum, Mollusk collection. 578 records from (Table 3) Relative abundances of selected planktonic foraminifera of ODP Site 117-722. 423 records from Bird Collection of Otto Hedin. 109504 records from Plant Specimens of Kurashiki Museum of Natural History. 11 records from Zoobenthos in surface sediments off Cape Lucul. 116 records from Phytoplankton abundance and species composition in the Sicily Channel in October 1991. 49 records from Pollen profile form Hickory Ridge Basin, Illinois, U.S.A. 6 records from Wiese. 209 records from Relative abundance of coccosphere-units at site GIK23414. 16 records from Coccolith counts of multinet M32/5_MSN986. 451 records from Nannofossil abundance of Hole 15-148. 21 records from Nannofossil abundance of Hole 6-55. 3 records from Nannofossil abundance of Hole 31-301. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/046-3. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/090-4. 818 records from Range chart of calcareous nannofossils from ODP Hole 188-1165B (Table 1). 3910 records from Plant (MNHM-PL). 746 records from RMT Trawl catch from the 1986/87 V7 AAMBER voyage. 216 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE236. 558 records from (Table 5) Pleistocene ostracodes from ODP Hole 104-644A. 1218 records from (Table 6) Relative abundances of the seven species of planktonic foraminifera from ODP Site 108-662. 1972 records from (Figure 6) Distribution chart of benthic foraminifers in ODP Site 126-792. 1691 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 1134 records from Ictiofauna de los corredores biológicos Sierra Madre del Sur y Selva Maya Zoque. 97 records from CNIN/Tipos Hymenoptera. 3 records from Analyses of the recent components of sediment core PS1215-2. 13225 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 1505 records from Relative abundance of planktonic foraminifera in Pliocene and Pleistocene sediments of DSDP Hole 32-310 from Hess Rise, Central North Pacific (Table II). 780 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 12 records from Abundance of microplankton from bottle APRIL-2000-K4. 108 records from Occurrence of mammalia relicts at site l´Abri du Flageolet I. 68 records from Planktic foraminifera abundance of Hole 22-213. 14137 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 15586 records from Historical quantitative benthos grab samples from the Southern Baltic Sea (EurOBIS). 117 records from (Table T1) Nannofossil abundance of volcaniclastic and other lithologies from ODP Hole 197-1203A. 274 records from Foraminifera abundance of sediment core BM1958.631. 19 records from Occurrence of mammalia relicts at site Gröbern. 320 records from Range table from planktonic foraminifers in ODP Hole 141-863A. 33 records from Range table from planktonic foraminifers in ODP Hole 175-1078B. 394 records from Range table from benthic foraminifers in ODP Hole 144-871C. 3 records from Microfossil abundance of Hole 50-415. 268876 records from Fiji Terrestrial Arthropods. 662 records from RSPB - Snipe survey of key sites in Britain in 2006 (RSPB and Natural England). 3204 records from Faunal Inventory of Morysin Nature Reserve. 73 records from VFD-HH/SH: Pferdweide Lammert. 357 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 1351 records from Neogene palynomorpha from site 93-603, part 1. 176 records from Range table from planktonic foraminifers in ODP Hole 159-961A. 99159 records from Biological Records Centre - Dragonfly and Damselfly (Odonata) records for Britain to 1992, from the former Dragonfly Recording Scheme. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 177466 records from CAS Entomology (ENT). 252060 records from Moths Ireland. 22 records from Phytoplankton abundance at bottle station GOM6/1. 4 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/107-5. 23 records from Planktonic foraminifera in ODP Hole 112-688A (Table 1). 21795 records from Computarización de la colección de abejas (Hymenoptera: Apoidea) del Museo de Zoología Alfonso L. Herrera, de la Facultad de Ciencias de la UNAM. 921 records from Importancia de las lombrices de tierra (Oligochaeta) en el monitoreo de áreas prioritarias de conservación del centro, este y sureste de México. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 26 records from Planktic foraminifera abundance of Hole 20-200A. 126 records from Planktic foraminifera abundance of Hole 32-305. 2 records from Abundance of benthos infauna at station GIK23025-2. 89762 records from Ornitho.eus. 45 records from Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam.. 1 records from Zetes latirostris. 20 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2004. 93 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cotingidae. 8 records from Pollen analysis of sediment profile BUA1 from Buchsee. 101 records from MVZ Mammal Observations (Arctos). 10 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 31 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 3594 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 240 records from Range table from benthic foraminifers in ODP Hole 175-1075A. 769 records from Range table from benthic foraminifers in ODP Hole 145-883B. 400 records from Phytoplankton abundance in surface water in October 1997, Callao, Peru. 169 records from Whale log - observations from ANARE voyages. 300 records from Plant (SMNH-PL). 9719 records from The Orchid Atlas of Western Australia. 1849 records from National Trust - Heigham Holmes species data held by The National Trust. 875 records from Fish monitoring data in Lake Kasumigaura. 1207 records from Calcareous nanofossils in late Pliocene sediments of ODP Site 162-982. 28 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 117 records from Wassermann. 81 records from Umgebung des Spalatin Gymnasium Altenburg. 61 records from Fürstenberger Ralley Teil 3. 430 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23068-3 in the Norwegian Sea. 87 records from Plasm bearing foraminifera counts from M35/1_MSN1049. 160 records from Plasm bearing foraminifera counts from M35/1_MSN1068. 128 records from Total foraminifera counts of multinet M33/1_MSN1030. 66 records from Plasm bearing foraminifera counts of multinet M21/2_MSN642. 54 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211660-6. 7 records from Abundance of nematoda in sediment profile M3/1_018 from the Iberian deep sea basin (Table 5). 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/009-2. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/088-4. 10 records from Benthic macrofauna abundance of sediment core 13078-017. 308 records from Planktic foraminifera counts of sediment core V19-178. 535 records from Distribution of microorganisms in recent sediments of Kiel Bay. 5233 records from (Appendix A) Stable carbon and oxygen isotopes and paleoproductivity reconstructions for the last 550 kyr of ODP Hole 130-807A from the Ontong Java Plateau, Pacific Ocean. 82953 records from Vascular Plants, Observations, Oslo (O). 877 records from Benthic foraminifera distribution of sediment core ASV11-987 (ASV987). 29 records from Klimaoasen in Köln. 62 records from Plasm bearing foraminifera counts of multinet M21/5_MSN728. 110 records from Abundance of planktic foraminifera at CTD station M39/4_366CTD-22. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-18-1. 45 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/508-2. 18 records from Meiofauna abundance in sediment core 13368-015. 234 records from Phytoplankton samples - 2006/07 V3 SAZ-Sense. 1825 records from Galathea II, Danish Deep Sea Expedition 1950-52. 31082 records from MEXU/Plantas Vasculares. 16425 records from Coleção Entomológica Pe. Jesus Santiago Moure (Hymenoptera). 92 records from Nottekanal, Klasse 7 - 10. 88 records from Upper Aptian Niveau Kilian range chart of nannofossils in SE France. 14 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-070. 106100 records from Fish (NSMK-PI). 1 records from Zetes semirufus. 62324 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 8980 records from MEXU/Tipos de plantas vasculares. 257 records from Kernberge und Umgebung (Jena). 58 records from Lüner Holz (Lüneburg). 17 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB04 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 525 records from Planktic foraminifera abundance of Hole 94-609. 70 records from Exotic terrestrial flatworms, Macquarie Island. 34140 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 12 records from Abundance of epibenthic echinoderms at seafloor photography station M21/5_317. 80 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 1. 161 records from A conspectus of the native and naturalized species of Nephrolepis (Nephrolepidaceae) in the world. 280 records from (Figure 1d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3202. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 30 records from (Table 2) Benthic isopod species of the Ross Sea, their bathymetry and distribution in the Southern Ocean. 1 records from Occurrence of mammalia relicts at site Ballybetagh. 1494 records from CSIRO, Cruise SS200001, Marine Biodiversity, South and Southeast Australia, 2001. 1639 records from Avena wild species collection. (N.I.Vavilov Institute of Plant Genetic Resources (VIR)). 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 2 records from A remarkable new flightless Madrasostes Paulian, 1975 from Vietnam (Coleoptera Scarabaeoidea Hybosoridae Ceratocanthinae). 101 records from Birdrace-Herford-Birder-Herford. 5 records from Naturschutzgebiet Ahrmündung (Remagen). 13478 records from Herp Collection. 28 records from Occurrence of mammalia relicts at site Climauti II. 83 records from Planktic foraminifera abundance of Hole 14-135. 2357 records from Foraminifera abundance of Hole 17-167. 3119 records from Hormigas en cultivos de naranja (Citrus sinensis (L.) Osbeck) de la costa Caribe de Colombia. 18039 records from Sponges of Rathlin Island. 258638 records from R. L. McGregor Herbarium Vascular Plants Collection. 31 records from Description of a new species of Acestridium (Siluriformes: Loricariidae) from Colombia.. 17 records from Inventarios de Herpetos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 347088 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 1 records from Miriapodi di alcune grotte della Campania. 306 records from Camera trap database of Tiger from Rajaji National Park, Uttarakhand. 2 records from The Genus Criodion (Audinet-Serville, 1833) (Coleoptera, Cerambycidae): First Record for Panama. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 59 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 1 records from Planktic foraminifera abundance of Hole 8-72. 163 records from Planktic foraminifera abundance of Hole 32-313. 2259 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 1116766 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 881 records from Moluscos Marinhos de Augusto Nobre. 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 35 records from Gym Freyung. 3000 records from Colección Macroinvertebrados Acuáticos Universidad Católica de Oriente. 3860 records from (Appendix Table 1) Absolute abundances of benthic foraminifers in DSDP Hole 94-608. 10 records from Benthic macrofauna abundance of sediment core 12930-044. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2 records from Amphibia ZMK. 15 records from AKG-Bensheim. 9126 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 431 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 403 records from (Appendix A) Relative abundance of Emiliania huxleyi in sediment cores of the North Atlantic. 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 232262 records from MVZ Mammal Collection (Arctos). 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 119366 records from The digitization of plant specimens of NTU. 26 records from A revision of the western hemisphere Chalcoscirtus (Araneae: Salticidae). 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 918 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 252 records from RSPB - Black grouse leks in the Forest of Clunie, 2002-2010 (RSPB, SNH). 192273 records from Field Museum of Natural History (Zoology) Mammal Collection. 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 66035 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Micro Moths (BNHS) - 1820-2009. 7 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann).. 178 records from Total foraminifera counts of multinet M6/7_MSN148. 26 records from Microzooplankton abundance measured on water bottle samples at station PS65/570-4. 100 records from (Table 4) Distribution of nannofossils in DSDP Hole 87-583D. 501 records from Relative abundance of Neogene nannofossils at ODP Site 138-844 from the eastern equatorial Pacific. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 210 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 13736 records from MfN - Mallophaga Collection. 648 records from Korea Bird Distribution Atlas Database. 3634 records from Herpetological collection of National Museum of Nature and Science. 31 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-18. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-075. 85783 records from Birds (KIEE-BI). 1340 records from (Figure 2) Distribution of dinoflagellate cysts in the mid-Cretaceous of ODP Hole 101-627B. 463 records from (App 3) Relative contents of benthic foraminifera in sediments from Core ASV1200. 241 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 18379 records from Mycology Herbarium, Trondheim (TRH). 14202 records from Plant specimens of Hokkaido University Museum. 37641 records from Nordic Genetic Resources. 1115 records from Distribution of planktic foraminifera (200-630 µm) of sediment core M8_057-2 (Table 4). 398 records from Mooswald (Freiburg). 66 records from Foraminifera abundance of Hole 55-432A. 89 records from Benthic macrofauna abundance in surface sediments of the east Greenland continental slope (75° N section). 2120907 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 164 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 569 records from (Appendix A) Planktonic foraminiferal abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 1726 records from KTU Pinophyta. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-087. 1968 records from (Appendix B) Distribution of planktonic foraminifera at DSDP Hole 72-518. 30 records from Benthic foraminifera abundance of Hole 42-379A. 899 records from (Fig. 13) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 80-549 in the North Atlantic. 30 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 1092 records from Field Study Group of the Dutch Mammal Society (NL) - 2009 - Mammal Survey Serra da Estrela, Portugal. 3664 records from Primera caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 22625 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 32450 records from Naturalis National Natural History Museum (NL) – Invertebrate specimens from marine expeditions. 906 records from Digital Florula - Las Cruces Biological Station. 1161 records from CNIN/Triatominos (Hemiptera-Heteroptera-Reduviidae). 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1995-D2. 102 records from Range table from planktonic foraminifers in ODP Hole 169-1035D. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1095A. 23 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 2670 records from Colección Teriológica y Ornitológica de la Universidad Tecnológica del Chocó. 4 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 53 records from Planktic foraminifera abundance of Hole 29-281A. 401 records from Range table from planktonic foraminifers in ODP Hole 138-852B. 1 records from Results of palynological analysis of Hole 302-M0004C. 11 records from Collection Xiphosura SMF. 10121 records from Arachnologie - SMNG. 734 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Icteridae. 1471 records from EcoRecord - Bryophyte records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 4 records from Tropidomyrmex elianae, a new myrmicine ant genus and species from Brazil, tentatively assigned to Solenopsidini (Hymenoptera, Formicidae).. 73 records from Fossil (JNHM-FO). 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 154 records from Specimens from India at the NTNU University Museum in Trondheim. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 97 records from LauWi. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 48 records from Wahner Heide LK 12 Biologie. 92 records from Total foraminifera counts of multinet M26/1_MSN845. 6258 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 1 records from Zetes ephippiatus. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 20 records from Mikroorganismen. 114 records from BIRDRACE VIE will rock you!. 8 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 30-63 µm. 72 records from Faunal assemblage of sediment core TR149-35. 10183 records from Planktic foraminifera counts of sediment core MD95-2040. 135 records from Total foraminifera counts of multinet M11/1_MSN522. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 47 records from Foraminifera species abundances from tow TT007_3-MOC6. 4 records from Counts (3) of calcareous dinocysts along profile Stevns-Klint. 1306 records from Flora genérica de las gramíneas del estado de Tlaxcala. 37 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fraction. 852 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_88MC. 2233 records from Chrysomelidae of Poland. 105 records from Plasm bearing foraminifera counts of multinet M21/5_MSN731. 2 records from Kirchenforst. 9 records from Nannofossil abundance of Hole 60-455. 21 records from Nannofossil abundance of Hole 24-232A. 18 records from Benthic macrofauna abundance of sediment core 13201-002. 12 records from Ficha de Sonora aemula. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN649. 133 records from Total foraminifera counts of multinet PO247/2_MSN1381. 8 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-03-16. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-9. 30 records from Nannofossil abundance of Hole 8-71. 22 records from Nannofossil abundance of Hole 9-83A. 115 records from Nannofossil abundance of Hole 29-279A. 5 records from Distribution of Quinqueloculina sp. in sediment core 13078-017. 271 records from Planktic foraminifera counts of sediment core RC11-147. 51 records from (Table 8) Percent distribution of calcareous nannofossils at ODP Hole 125-781A. 2019 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 2070 records from (Table 4) Plio-Pleistocene benthic foraminifera of ODP Hole 107-652A. 15 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_13-CTD162. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-06-2. 9 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 64 records from Feuchtbiotop Weidenkaule. 56 records from Nannofossil abundance of Hole 94-607. 6 records from Benthic macrofauna abundance of sediment core 13077-019. 15 records from Benthic macrofauna abundance of sediment core 13078-013. 67 records from (Table 5) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 1496 records from (Table 4) Distribution of planktonic foraminifers in ODP Hole 108-658A. 49 records from Abundance of calcareous nannofossils across the K/T boundary at ODP Hole 113-690C (Table 1). 1249 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 3761 records from Mountain Invasion Research Network (MIREN) survey. 61234 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1999) (AfrOBIS). 30302 records from Arizona State University Amphibian and Reptile Collection. 5159 records from CNHE/Coleccion Nacional de Helmintos. 2128 records from Universitat de València, Colecciones de Criptógamas: VAL_Algae. 448 records from Harpactus Shuckard. 48 records from Freiheitsring (Frechen). 67 records from Occurrence of mammalia relicts at site l´Abri des Battuts I. 2945 records from (Figure 4) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Site 71-512. 54 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 3023 records from Flora y datos básicos para la evaluación de las actividades apícola y forestal en tres áreas focales del corredor Sian Ka'an-Calakmul. 998 records from Korean Ethnobotany Database. 195264 records from U.S.D.A. Forest Service, Redwood Sciences Laboratory - Lamna Point Count. 90 records from Schulhof Bühlschule Giengen. 73 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 1761 records from Centro de Recuperación de Fauna Silvestre "La Tahonilla". Cabildo de Tenerife. 576 records from Distribution of agglutinated foraminifers in sediment core Well 6407/9-3. 70 records from Parkuntersuchung Weißer See. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 9633 records from Coleção Entomológica do Depto. de Sistemática e Ecologia. 5 records from Analyses of the recent components of sediment core PS1400-4. 342 records from (Table A.10) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (150-500 µm). 131 records from Unser Schulhof - eine Apotheke. 34 records from Occurrence of mammalia relicts at site Felsdach Inzighofen. 241 records from Planktic foraminifera abundance of Hole 67-499B. 13 records from Collection Reptilia fossil SMF. 9 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (2000m section). 57 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Tityridae. 2324 records from Eriophyoid Mites of Poland. 11708 records from The Erysiphales Collection at the Botanische Staatssammlung München. 22 records from Sediment properties of core PLG95B_06BOXG. 592 records from Antarctic Krill occurrence data from Ukraine YUGNIRO Institute. 1142 records from Range table from planktonic foraminifers in ODP Hole 154-925A. 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 3941 records from UAFMC Mammals. 836971 records from Bernice P. Bishop Museum. 1069 records from ZFMK Sound Archive. 2775 records from (Table T4) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1050C. 12 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 19334 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 1 records from Notizen über Oribatei (Acari). III. 49 records from Additional records for Stenosagola newtoni Park & Carlton, 2013 (Staphylinidae: Pselaphinae: Faronitae), with notes on aedeagal morphology. 851 records from (Figure 2d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3245. 4303 records from Odonata Collection. 1741 records from Benthic foraminifera abundance of Hole 84-570, Part 1. 30 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-913B. 11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 2265 records from Algae, Specimens, Agder naturmuseum (KMN). 15 records from Additions to the ichthyofauna of the Tristan da Cunha Group, South Atlantic Ocean.. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 39 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 47 records from Schulgelände Ceciliengymnasium. 5733 records from Small Mammal Research Database. 372 records from Colección de Entomología - Arthropoda. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 496 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 48 records from Trockenrasen bei Dörndorf. 135 records from Total foraminifera counts of multinet M21/3_MSN688. 186 records from Total foraminifera counts of multinet M21/1_MSN604. 45 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1385. 23 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5136-1. 94 records from Coccolith counts of multinet SO119_MSN1298. 414051 records from Entomology, Natural History Museum, University of Oslo. 98423 records from Insect species recorded in sugarcane fields of Khon Kaen Province, Thailand, over three seasons in 2012. 56302 records from Kathryn Kalmbach Herbarium. 84521 records from BioGIS - Vascular plants - INPA database. 160 records from Wirbach-Taubental (Bad Blankenburg). 1894 records from Colección viva Jardín Botánico Universidad Tecnológica De Pereira. 103 records from BIRDRACE Die Otzberger. 215 records from (Table 2) Distribution of sinsitral and dextral fohsellids in middle Miocene sediments of ODP Hole 130-806B from the Ontong Java Plateau, Pacific Ocean. 170 records from Scottish Natural Heritage - The occurrence and distribution of Najas flexilis (Slender naiad) in Loch of Craiglush, Loch of the Lowes and Loch of Butterstone. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 6 records from Nannofossil abundance of Hole 7-63. 76 records from Coccoliths in sediment core PS1533-3. 30 records from Southern Ocean oligochaete occurrence data - a literature-based compilation. 31 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part III. 708 records from Phytoplankton samples - 2005/06 V3 BROKE-West. 1551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5. 771 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 84 records from BIRDRACE Birding for Nature. 482 records from Total foraminifera counts of multinet M6/7_MSN91. 21 records from Phytoplankton abundance at the sea bottom off Sechura in january 2007, Peru. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_5-CTD56. 2268 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-173-3. 6 records from Phytoplankton abundance at station Rigel_1_2005-03 in March 2005, Chipana, Chile. 7 records from Abundance of nematoda in sediment profile M3/1_029 from the Iberian deep sea basin (Table 5). 19 records from Nannofossil abundance of Hole 31-298. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/107-5. 109176 records from Herps Specimens. 44 records from (Table 6) Distribution of nannofossils in DSDP Hole 87-583G. 57 records from Nannofossil abundance in sediment core PS1311-4. 315 records from Planktic foraminifera counts of sediment core RC17-69. 227 records from (Table 6) Chemical composition of basalts from the Mid-Atlantic Ridge in the Doldrums Fault Zone. 130 records from (Table 15) Distribution of ostracode species in Core PS51/135-4. 1473 records from (Appendix 2, Part 1) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-689. 43 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV30_1. 47 records from Université Pédagogique Nationale de Kinshasa (UPN) - Plantes fourragères de la République démocratique du Congo - Projet CABIN. 9 records from (Table 2) Macrobenthos on the floor of the West Bay of the Furugelm Island, Sea of Japan. 1541 records from (Appendix B3) Calcareous nannofossils of ODP Site 208-1263. 1191 records from Relative abundance of Neogene nannofossils at ODP Site 138-850 from the eastern equatorial Pacific. 566 records from (Appendix A1) Distribution of benthic foraminifera in ODP Site 184-1143. 46400 records from Museu Paraense Emilio Goeldi - Ophidia Collection. 506 records from Range table from benthic foraminifers in ODP Hole 146-889A. 4051 records from Homoptera. 51 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 54059 records from Pelagic Fish Observations 1968-1999. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 1 records from Hausgarten. 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 1355 records from Collection Crustacea ZMG. 141 records from Fig. 7. Relative abundance of ostracod species in composite core JH05. 886 records from Lepidoptera Observations from New Zealand by Donald Hobern. 354 records from Relative abundance of planktonic foraminifera in sediment core L-66. 9 records from Analyses of the recent components in the sand fraction of sediment core PS1217-1. 315232 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 1028827 records from SEAMAP - marine mammals, birds and turtles. 5512 records from Vascular Plants Collection of National Museum of Nature and Science. 32762 records from Fish tag database. 93 records from CCUG Microorganisms databases(Fungi). 667 records from Antarctic Krill occurrence data from Discovery expeditions. 302 records from Stadtpark Sulzbach-Rosenberg. 195 records from Occurrence of mammalia relicts at site Weinberghöhlen/Mauern. 778 records from Planktic foraminifera abundance of Hole 40-362. 1 records from Planktic foraminifera abundance of Hole 54-420A. 774 records from Planktic foraminifera abundance of Hole 80-549A. 1731 records from (Figure 3) Range of selected planktonic foraminifera in Paleocene samples of DSDP Hole 93-605. 17980 records from Impetus - Herbarium Hamburgense. 6 records from Sediment properties of core PLG93_BCORE1. 154 records from Planktic foraminifera distribution of sediment core TRI171-27. 97 records from Schulgelände Regelschule Gorndorf/ Umgebung Jugend- und Stadtteilzentrum Gorndorf. 168 records from Weidenhüttendorf an der Würm (München). 2 records from Occurrence of mammalia relicts at site Dechenhöhle. 318 records from Nematode abundance in cold seep sediments of the Darwin mud volcano. 57 records from Range table from planktonic foraminifers in ODP Hole 152-915A. 862 records from (Appendix A4) Planktonic foraminifera of ODP Hole 172-1062B. 107 records from BIRDRACE Herford Birders. 195 records from Total foraminifera counts from multinet M31/3_MSN923. 85 records from Plasm bearing foraminifera counts from M35/1_MSN1053. 331 records from Size of planktic foraminifera at CTD station PS55/082-1. 65 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211670-7. 11 records from A new species of the catfish genus Akysis (Siluriformes: Akysidae) from southern Borneo.. 12 records from Abundance of radiolaria at station LV28-40-2. 311 records from Avena wild species VIR Herbarium. N.I.Vavilov Institute of Plant Genetic Resources (VIR). 2 records from New data on the rare Afrotropical scarab beetles Orphnus drumonti Frolov and Delopleurus naviauxi Frolov et Cambefort (Coleoptera, Scarabaeidae, Orphninae and Scarabaeinae). 1853 records from Yeast Collection in BCRC. 19 records from Three new Scandinavian species of Culicoides (Culicoides): C. boyi sp. nov., C. selandicus sp. nov. and C. kalix sp. nov. (Diptera: Ceratopogonidae). 1 records from Nothrus biverrucatus. 6062 records from Lichens of Knyszyn Forest. 43066 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 1418 records from Fossil (GNHM-FO). 1709819 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 184156 records from The Flora of County Waterford. 66 records from Mammals (KIEE-MM). 16 records from Scorpaena bulacephala, a new species of scorpionfish (Scorpaeniformes: Scorpaenidae) from the northern Tasman Sea.. 5549 records from Diplopoda (NSMK-DI). 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 44 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 3947 records from Institut Menorquí d'Estudis. Colección Histórica de Rodríguez Femenías, Herbarium Generale Minoricae: HGM-Femenias. 8858 records from (Appendix 2a) Foraminiferal analyses of research borehole Sonder Vium. 1 records from Zetes cespitum. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 530 records from Collection Crustacea - KAUMM. 588 records from Relative abundance of ostracods in sediment core Lz1120. 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 235 records from Total foraminifera counts from multinet M31/3_MSN905. 59 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/424-22. 40 records from Stable carbon and oxygen isotope ratios of calcareous dinoflagellate cysts and planktic foraminifera from the Campanian/Maastrichtian section of ODP Hole 113-690C in the Weddell Sea (Table 1). 24 records from Abundance and carbon biomass of phytoplankton at station TT007_7-CTD88. 12 records from Abundance of microplankton from bottle APRIL-2000-K2. 1201 records from monocotyledonous_geophytes_of_fergana_valley. 4 records from First verified record of the ant genus Calyptomyrmex (Hymenoptera: Formicidae) from India, along with a revised key to known Indomalayan species. 74 records from SuLaMa reptile monitoring. 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 127 records from Distribution of planktonic foraminifera of sediment core SH1972_2. 306 records from (Table DR1) Biofacies, percentages of important benthic foraminifera and isotope data at ODP Site 758. 34586 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 14 records from Benthic macrofauna abundance of sediment core 12930-093. 86 records from Fliegenhaupt Marksuhl. 1130 records from Ostracoda in sediment core PS51/154-11. 265 records from CNIN/Mantodea. 1 records from Pollen and spore abundance of Hole 42-379A. 2880 records from Coleoptera, NEF. 2 records from A New Species from Mountain Forest Soils in Japan: Porosia paracarinata sp. nov., and Taxonomic Concept of the Genus Porosia Jung, 1942. 2 records from Lubbockichthys myersi, a new species of dottyback fish from Guam (Pseudochromidae: Pseudoplesiopinae).. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 372 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 320 records from Myxomycetes collection of the University of Eastern Finland. 441 records from Pollen analysis of surface samples from Germany and Austria. 766 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Peces. 1618 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during two Michael Sars cruises in 2000. 176 records from INSECT COLLECTION. 365 records from Bird Specimens of Miyazaki Prefecture Museum of Nature and History. 353 records from Planktic foraminifera distribution of sediment core GIK17940-2. 93 records from Südwestlich der Parkwiesen. 40 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 12 records from Microplankton abundance at bottle station SEPT-1999-K9. 107 records from Planktic foraminifera abundance of Hole 18-180. 165 records from (Table 3) Ostracode distribution in ODP Hole 122-761C. 14 records from (Table 4b) Abundances of Globorotalia menardii in sediment core INMD-115BX. 25471 records from Ibaraki Nature Museum, Arthropoda collection. 30985 records from MEXU/Asteraceae. 4660 records from Distribution of planktonic foraminifera of site GeoB1105. 4554 records from Planktic foraminifera counts (census) of sediment core MD96-2080. 88 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station NOVEMBER-1994-D4. 25 records from Benthic foraminifera abundance of Hole 1-4. 164 records from Range table from benthic foraminifers in ODP Hole 192-1186A. 254 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 2000 records from (Table A2) Sea surface temperature reconstruction of DSDP Site 94-607 in the North Atlantic. 3483 records from Irish National Frog Database. 201 records from Mammals in MZNA-VERT: project CAS. 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 63-125 µm fraction. 88 records from Total foraminifera counts of multinet SO118_MSN1265. 30 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 24 records from (Table 7) Distribution of Pleistocene to Miocene nannofossils in ODP Hole 108-661A. 99 records from Planktic foraminifera abundance of Hole 94-610E. 2 records from Benthic foraminifera abundance of Hole 42-376. 81 records from Range table from benthic foraminifers in ODP Hole 172-1061C. 210 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction > 20µm. 2839 records from Rocky Shore Macroalgae. 12 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 584 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust Shoresearch. 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 256 records from BIRDRACE Upupa epöpse. 5 records from Memorial University Botanical Garden Collection. 252 records from Range table from planktonic foraminifers in ODP Hole 155-934A. 96 records from Range table from planktonic foraminifers in ODP Hole 182-1126D. 16 records from Qualtitative analysis of calcareous dinocysts along profile Stevns-Klint. 18 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 141-860B. 99 records from VFD-BW, Albvorland: Pferdeweiden Ofterdingen. 8 records from UWYMV Herpetology Collection (Arctos). 10885 records from RSPB - Swift Inventory of Nest Sites in the UK, 2009 (RSPB and Swift Conservation Groups). 70 records from Tab. A6: Anzahl von M. balthica während der Ansiedlungszeit. 422 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 1134 records from Alterra (NL) - Microarthropods inventory in European countries. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 1 records from A new species of the genus Sinanapis (Araneae: Anapidae) from Lam Dong province, southern Vietnam.. 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 45 records from Plasm bearing foraminifera counts from multinet SO119_MSN1286. 77 records from Total foraminifera counts from M35/1_MSN1075. 51 records from Plasm bearing foraminifera counts of multinet M21/5_MSN732. 26 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1368. 337 records from Abundance of calcareous dinocyst along profile Calais-Escalles. 12 records from Abundance of radiolaria at station LV28-44-1. 458 records from (Appendix Table 4) Distribution of dead benthic foraminifera in surface sediments. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/042-2. 1030627 records from Phanerogamic Botanical Collections (S). 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 145 records from privater Garten. 16 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 63-125 µm fraction. 1294 records from Global Butterfly Information System (GloBIS). 9 records from Microzooplankton abundance and biomass at station TT043_9-1. 611 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Chavez 2011. 524 records from (Table 2) Benthic foraminiferal composition at University of Texas Marine Science Institute (UTMSI) piston cores at Costa Rican slope sediments. 356 records from Biotope in Rheine - Aktion 350. 6 records from Nannofossil abundance of Hole 55-430B. 3512 records from (Table 3) Plio-Pleistocene benthic foraminifera of ODP Hole 107-653A. 2723 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Cirolana00/5. 7966 records from MfN - Phasmid Collection. 2 records from Nothrus palustris. 365 records from Colección Herpetológica de la Patagonia. 228 records from Total foraminifera counts of multinet M36/6_MSN1193. 66 records from Foraminifera species abundances from tow TT007_10-MOC20. 46 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Caprimulgidae. 1312 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 177 records from Donauinsel des BN bei Entau. 50 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 116 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 120-748. 3 records from Antarctic Arrow worms. 243 records from (Table 3) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-749B. 144 records from BIRDRACE Punkbirder Helgoland. 27 records from (Table 12) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-666A. 1729 records from Biodiversidad de Datura (Solanaceae) en México. 9728 records from Birds of Ireland. 924 records from Antarctic Fur Seal Populations on Heard Island Summer 1987-1988. 320 records from Planktic foraminifera assemblage in sediment core GIK11944-1. 3978 records from Colección de Entomopatógenos de México (CNRCB). 92 records from Range table from planktonic foraminifers in ODP Hole 167-1017B. 91 records from Benthic foraminifera abundance of Hole 84-569A. 350 records from (Table 4) Abundance of planktonic foraminifera in ODP Hole 113-690C, small size fraction. 21 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-120BX. 679 records from Results of palynological analysis of Hole 302-M0004A. 2079 records from (Table 1) Occurrence and frequency of benthic foraminifera in Paleocene samples of DSDP Hole 93-605. 3 records from Mammalia (SMNH-MM). 35 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rhinocryptidae. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 11 records from Phytoplankton abundance at station Sechin_2003-07-15_1, Casma, Peru. 1271 records from Distribution of planktonic foraminifera of sediment core Core190. 107 records from 1st Austrian Birdrace (Wien). 279 records from Planktic foraminifera abundance of Hole 11-98. 2402 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 13646 records from Senckenberg - CeDAMar Resource. 292 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 3 records from Ctenosciara alexanderkoenigi sp. n. (Diptera: Sciaridae), an exotic invader in Germany?. 19309 records from Mammal collection, Natural History Museum, University of Oslo. 214 records from Binsenwiesen. 347 records from (Table 4) Standing stock values of important species in surface sediments. 17 records from (Table 2) Madreporarian corals collected in the Canary upwelling area. 313162 records from Observational database of Icelandic plants. 296 records from DJH. 2148 records from Eppingen und Umgebung. 76 records from Occurrence of mammalia relicts at site Vindija. 3952 records from Range table from benthic foraminifers in ODP Hole 159-962D. 11 records from Observation of birds at station PS14/156 along 49° West. 599 records from NHT flora. 2268 records from (Table 1) Distribution of Cretaceous-Tertiary benthic foraminifers in ODP Hole 129-802A. 7938 records from Hymenoptera collection, Natural History Museum, University of Oslo. 153 records from Selztal bei Friesenheim. 36 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12594-2. 181 records from Total foraminifera counts from multinet M31/3_MSN914. 45 records from Nannofossil abundance of Hole 28-265. 63 records from Matter enrichment of the macrofauna community of MAC station 12930-005. 68 records from Range table from benthic foraminifers in ODP Hole 144-873B. 2306 records from (Table T4, T5, T6, T7) Percentage of agglutinated and calcareous benthic foraminiferal species in ODP Hole 178-1098C. 44 records from Flora und Fauna in unserer Kita. 19557 records from Collection Thysanoptera SMF. 54 records from Outer Hebrides Biological Recording Project - OHBRP Vertebrates (except birds and restricted records) Dataset - Outer Hebrides. 90 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 6394 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 29 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 139 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 53985 records from BioMar - LIFE project. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 7427 records from Weevils of the Tatra Mts.. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 5 records from Streuobstwiese (Mittelgasse 4). 18 records from Landschaftsschutzgebiet Buchhorst2. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction 63-150 µm. 34 records from Marine Conservation Society - Palinurus elephas or Crawfish sightings in the UK and Ireland from 1969 to the present time.. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 102 records from Plasm bearing foraminifera counts of multinet M12/3_MSN559. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 102 records from Foraminifera species abundances from tow TT011_11-MOC72. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 1 records from Erysipelothrix inopinata sp. nov., isolated in the course of sterile filtration of vegetable peptone broth, and description of Erysipelotrichaceae fam. nov.. 1826 records from Collection des Mollusques (BOUM). 1 records from Celaeno spinosa. 49637 records from Monitoring data from the federal state Hesse (Germany). 87 records from Klütwald. 57 records from Garten in Schmölln. 152 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-35. 16 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 122 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1359. 49 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core PS1246-2. 24 records from Content of coarse fraction and G. menardii in sediment corev V25-43. 25 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_8-CTD93. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-15-3. 14 records from Phytoplankton abundance at station Sechin_2003-09-18_1, Casma, Peru. 5 records from Distribution of meiobenthos in sediment core M19_201-2 of the northeastern Atlantic (Table 1). 24 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2446-2. 21 records from Meiofauna abundance in sediment core 13077-006. 4 records from Estimated plankton abundance at station PS63/064-6. 12 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-131BX. 42 records from Was singt im Duvenstedter Brook. Wir zählen die Brutvögel im Naturschutzgebiet. 8649 records from Fossil (WSHN-FO). 343 records from Collection Cnidaria - ZMB. 195 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 316 records from (Table 2) Distribution of planktonic foraminiferal tests in sediments from Core ML7_475. 41460 records from Herbarium (UNA). 117 records from Muskox Abundance. 9371 records from Range table from planktonic foraminifers in ODP Hole 152-918D. 11 records from Range table from planktonic foraminifers in ODP Hole 178-1096C. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 8 records from Pollen and spore abundance of Hole 42-380. 494248 records from British Lichen Society - BLS Mapping Scheme dataset, 1750-2009. 6987 records from National Trust - Ickworth species data held by The National Trust.. 11268 records from Aphidoidea Collection. 1 records from Damaeus auritus. 6422 records from Ájtte. 36613 records from Inventaire National du Patrimoine Naturel : Amphibiens et Reptiles de France (Enquête 1). 5042 records from Tracheophyta collection of Biodiversity Center of Japan, Ministry of Environment. 5995 records from Insect (HUNM-IN). 193 records from Total foraminifera counts of multinet M21/3_MSN663. 1215 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán. 2088 records from Benthic foraminifera of sediment core MD99-2286. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 2784 records from (Figure 3) Distribution of benthic foraminifers in the Albian of DSDP Hole 71-511. 20973 records from Real Jardin Botanico, Madrid: MA-Funhist. 96 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 99 records from Occurrence of mammalia relicts at site l´Abri de Combe-Cullier. 2970 records from (Table 2) Distribution of planktonic foraminifera in the latest Oligocene to Holocene section of ODP Hole 149-897C. 154124 records from Arizona State University Lichen Collection. 718 records from Zukünftiges NSG Höftland/Bockholmwik. 57 records from Occurrence of mammalia relicts at site Moladova V. 14 records from Occurrence of mammalia relicts at site Crumstadt 1. 1 records from Planktic foraminifera abundance of Hole 8-73. 198 records from Phytoplankton abundance in surface water in January 1996, Pisco, Peru. 8640 records from Fossil (WSHN-FO). 764 records from BioGIS - Fish - INPA database. 1042 records from Planktic foraminifera abundance of Hole 37-333. 1 records from Range table from planktonic foraminifers in ODP Hole 174-1072A. 3 records from Range table from planktonic foraminifers in ODP Hole 183-1141A. 96 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 246 records from Benthic foraminifera abundance of Hole 73-524. 131 records from Range table from benthic foraminifers in ODP Hole 189-1172A. 300 records from Gunma Museum of Natural History, Fish Specimen. 578 records from (Figure 2c) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3239. 12768 records from (Table 4) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-872C. 190242 records from Mycology herbarium, Oslo (O). 13 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Laguna Las Barrancas (Spitznagel, octubre 1999). 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 33 records from Astyanax endy (Characiformes: Characidae), a new fish species from the upper Río Bermejo basin, northwestern Argentina.. 22 records from Synonymy of Homalopoltys (Araneae: Araneidae) with the genus Dolichognatha (Araneae: Tetragnathidae) and descriptions of two new species. 5 records from Aretidris, a new genus of ants (Hymenoptera: Formicidae: Myrmicinae) from the mountains of Luzon Island, Philippines. 10189 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 233 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 1303 records from Mid Ulster Hare Surveys 2012-2015. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 47499 records from Sphaeroceridae Collection. 20416 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 133656 records from NINA insect database. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 1952 records from ISM Ichthyology Collection. 767 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 30129 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 1 records from Flora of Suriname, volume VI, part I. 144765 records from Invertebrates Collection of the Swedish Museum of Natural History. 8 records from Krittenhorster Wald (Ostkilver). 114 records from BIRDRACE Di-Bi-Di-Birder. 50 records from Plasm bearing foraminifera counts from M35/1_MSN1047. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 74 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core GIK23059-2. 18026 records from Herbario micológico de La Universidad de La Laguna, Tenerife: TFC_Mic. 2 records from Nannofossil abundance of Hole 6-49. 6 records from Planktic foraminifera abundance of Hole 23-226. 352 records from Universidad de Málaga: MGC-Lichen. 44 records from Total foraminifera counts of multinet M21/4_MSN721. 40 records from (Supplementary Table 2) Estimates of bottom-water oxygenation at site GeoB11185-1. 276 records from Planktic foraminifera from surface sediments of the Indian and Pakistan continental margin (Table 1). 2 records from Microzooplankton abundance and biomass at station TT050_19-3. 1 records from Microzooplankton abundance and biomass at station TT054_24-22. 3 records from Sarcodine counts and carbon biomass at station TT012_5-TM28. 145 records from Phytoplankton abundance at station CD46_0405C#7. 16 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 144 records from Planktic foraminifera of surface sediments off Portugal and Morocco (Table 4). 497 records from Especies de Leptohyphes (Insecta: Ephemeroptera: Leptohyphidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 83 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 129 records from Benthic macrofauna abundance of subcores of sediment core 12930-084. 11300 records from Eastern Canada Benthic Macro Fauna (OBIS Canada). 189 records from (Table A.09) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (125-250 µm). 141 records from Schulhof und Anlagensee in Nellingen. 53 records from Occurrence of mammalia relicts at site Roter Berg bei Saalfeld. 456 records from Range table from benthic foraminifers in ODP Hole 144-873A. 1626 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1119. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 15 records from Diatom abundance measured on water bottle samples at station PS58/009-2. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 30008 records from Lepidoptera specimen database of Japan. 1295 records from Planktic foraminifera counts of sediment core RC08-49. 921 records from Planktic foraminifera counts of sediment core RC14-37. 27828 records from svalbardflora.net. 9 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-7. 262 records from (Appendix 6) Stable oxygen isotope record of Globigerina bulloides and abundance of Neogloboquadrina pachyderma in sediment core MD95-2041. 9187 records from (Table 14) Ranges of benthic foraminifers through the Neogene in ODP Hole 115-714B. 1530 records from (Appendix B) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747C. 3982 records from Plant (GFEI-PL). 127 records from Collection Hydrozoa - ZMB. 18894 records from (Table 5) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Site 114-702. 11340 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 86 records from Pollen analysis of sediment core GIK16856-2. 426 records from Myriapoda - SMF. 29002 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. Coleóptera. 606 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Plantas. 314 records from (Appendix 1a) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber in the Holocene section of sediment core GeoTu_SL096. 2 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 55 records from (Table 2c) Species compositioon of planktonic foraminiferas in bottom sediments from Core ML1_66. 39 records from Mineralogy of serpentine muds of ODP Leg 125 holes (Table 1). 1154 records from Collection Plecoptera - SMF. 1023 records from Spencer Entomological Museum. 2483 records from Bacteria collection of National Institute of Public Health, Poland. 193 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V27-86. 9031 records from Herbario Kew del Real Jardín Botánico (RBGKEW). 20 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB06 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 269 records from 3. Tag der Artenvielfalt Hockenheim. 15 records from Spiders of the genus Habrocestoides from China (Araneae: Salticidae). 177 records from (Table 11) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-589. 2346 records from (Fig. 8) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 44-391C in the North Atlantic. 1139 records from Phytoplankton abundance in surface water in September 1996, Ilo, Peru. 631 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 10567 records from Coleoptera collection of National Museum of Nature and Science. 5336267 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 55 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2008. 127 records from Range table from planktonic foraminifers in ODP Hole 171-1053B. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1100C. 159 records from Range table from planktonic foraminifers in ODP Hole 180-1109C. 84 records from North Carolina State Museum of Natural Sciences Fishes Collection. 212 records from (Table T4) Planktonic foraminifera abundance of ODP Site 170-1042 sediments. 82230 records from UPCB - Herbário do Departamento de Botânica. 82 records from Countryside Council for Wales - Non-native species records from Countryside Council for Wales (CCW) non-native monitoring research and ad-hoc sightings. 39582 records from MSB Bird Collection (Arctos). 43 records from Bryconops magoi and Bryconops collettei (Characiformes: Characidae), two new freshwater fish species from Venezuela, with comments on B. caudomaculatus (Gunther).. 1387 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 61 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/546-19. 10000 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 13 records from Description of lithologic section units of IODP Hole 325-M0031A. 692 records from Planktic foraminifera abundance of Hole 40-360. 94 records from Planktic foraminifera abundance of Hole 80-550. 156 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 63 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_INSECTA. 1251 records from Visual Plants (144.41.33.158) - Herbarium specimen from "EA", Kenya. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 1 records from Antarctic Marine Amoebae. 677 records from Meiofauna abundance of central Mediterranean Sea mud volcano sediments. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 1 records from Pelops phaeonotus. 2 records from Parvimyrma gen. nov. belonging to the Solenopsis genus group Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 55 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 22 records from Colección Parasitológica del Centro Nacional Patagónico (CNP-PAR). 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 767 records from BioGIS - Bats - Asaf Tsoar database. 81329 records from natagora-earlybirds. 820552 records from Fauna Atlas N.T.. 10168 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves en el complejo de páramos Cruz Verde - Sumapaz. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 2916 records from Orthoptera (Grasshoppers & Crickets) & allied insects of Ireland. 829 records from Cambridgeshire & Peterborough Environmental Records Centre - Chippenham Fen Moth surveillance project. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 30 records from Leben auf einer Sturmfläche. 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 137 records from Abundance of planktic foraminifera at CTD station PS55/077-1. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-06-4. 316 records from Planktic foraminifera counts of sediment core V14-101. 615 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part I. 1 records from Diatom abundance of Hole 95-613. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 27 records from Zwickau- Schwanenteich. 163 records from Tiere und Pflanzen am Pfannenbach. 4 records from Distribution of meiobenthos in sediment core M23_123 (2) of the northeastern Atlantic (Table 1). 56034 records from Fish Specimens. 34 records from Urolophus kapalensis sp. nov., a new stingaree (Myliobatiformes: Urolophidae) off eastern Australia.. 11 records from Nannofossil abundance of Hole 6-56B. 14 records from Nannofossil abundance of Hole 85-573. 159 records from Plasm bearing foraminifera counts of multinet M21/1_MSN606. 92 records from Plasm bearing foraminifera counts of multinet M26/1_MSN843. 87 records from Total foraminifera counts of trap L2_92_B49. 785 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-19-2. 10 records from Phytoplankton abundance at station Rigel_6_2005-02 in Febraury 2005, Chipana, Chile. 5 records from Tuttlinger Tag der Artenvielfalt. 4 records from Nannofossil abundance of Hole 29-281A. 39033 records from SBMNH Vertebrate Zoology. 28 records from Nannofossil abundance of Hole 26-253. 18 records from Meiofauna abundance in sediment core 13200-012. 95 records from Ibaraki Nature Museum, Amphibians and Reptiles collection. 577 records from Estación Experimental de Zonas Áridas (CSIC): EEZA-Herpet. 180 records from (Table 7) Distribution of the large, few-chambered Globigerinelloides species in DSDP Hole 79-545. 1393 records from Lepidoptera from Rancho Grande, Rondônia, Brasil. 66 records from Occurrence of mammalia relicts at site Malerfels_I. 73 records from Planktic foraminifera abundance of Hole 2-11. 18 records from Planktic foraminifera abundance of Hole 32-310. 759 records from Planktic foraminifera abundance of Hole 47-398D. 878 records from Planktic foraminifera abundance of Hole 84-568. 6930 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 14219 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 13865 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 1664 records from Zooplankton of the Eastern South Pacific (OBIS South America, SOUTH PACIFIC NODE). 501 records from Planktic foraminifera assemblage in sediment core SU90-I03. 190 records from Foraminifera abundance of sediment core MD81-LC07. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 3 records from Analyses of the recent components of sediment core PS1215-2. 668 records from Naturschutzgebiet Sistig-Krekeler-Heide. 973 records from Range table from planktonic foraminifers in ODP Hole 157-954B. 3 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 1269 records from Distribution of benthic foraminifers (living) in surface sediments (Table 4). 32 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 1 records from The Oribatid Family Phthiracaridae I. Introduction and Redescription of Hoplophthiracarus pavidus (Berlese). 3 records from A new species of Lygistorrhina Skuse (Diptera: Sciaroidea: Lygistorrhinidae) from South Africa. 4 records from The Afrotropical Miomantis caffra Saussure 1871 and M. paykullii Stal 1871: first records of alien mantid species in Portugal and Europe, with an updated checklist of Mantodea in Portugal (Insecta: Mantodea). 70 records from Planktic foraminifera abundance of Hole 84-569A. 15 records from Range table from planktonic foraminifers in ODP Hole 169-1036A. 1512 records from Benthic foraminiferal assemblages across the Cretaceous Paleogene boundray of ODP Site 208-1262 on Walvis Ridge, eastern South Atlantic. 72636 records from Insect Collection of Taiwan Forestry Research Institute. 7 records from Additions to the myxobiota of the Åland Islands. 4024 records from Sightings Map of Invasive Plants in Portugal. 86556 records from NINA Vanndata øvrige arter. 20 records from Motzener Tonsee. 244 records from WildesMoor bei Schwabstedt. 13 records from Tag der Artenvielfalt am Bruckenwasen. 161 records from BIRDRACE Nord-Seh-Team. 930 records from Benthic foraminifera counts of sediment core PS2644-5. 56 records from Range table from planktonic foraminifers in ODP Hole 167-1010C. 923 records from Collection Graptolithina fossil SMF. 1 records from Abundance of benthos infauna at station GIK23004-3. 1322 records from Targeting a portion of central European spider diversity for permanent preservation. 1042 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 4 records from Arthropoden aus südostalpinen Höhlen.. 39 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 50834 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 3621 records from Millenium Seedbank (MSB). 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 26368 records from Marie-Victorin Herbarium (MT) - Bryophytes. 190 records from ENBI-Dataset of GART-GloBIS. 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 356 records from Morphologische Daten von Puffinus creatopus. 372 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 99 records from Düne am Ulvenberg (Darmstadt). 126 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 147 records from Total foraminifera counts of multinet M36/6_MSN1195. 82 records from Foraminifera species abundances from tow TT011_5-MOC63. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 25128 records from rmca-albertine-rift-butterflies. 115 records from Plasm bearing foraminifera counts of multinet M21/1_MSN614. 517 records from (Appendix B Table 2) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB2204-2. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-12-1. 5 records from Distribution of meiobenthos in sediment core M19_216-2 (2) of the northeastern Atlantic (Table 1). 3 records from Nannofossil abundance of Hole 51-417D. 18 records from (Table 1) Early Miocene and late Oligocene ostracods in sediment core CRP-2A. 68 records from Macrofauna abundance in surface sediment sampled during cruise DI229. 133 records from Catalogue of type specimens of fungi and lichens deposited in the Herbarium of the University of Granada (Spain). 60000 records from Birds (NSMK-BI). 144 records from Total foraminifera counts of multinet M21/2_MSN640. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 24 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD11. 26 records from Ostracoda abundance of Hole 13-132. 988 records from Distribution of foraminiferal fauna from ODP Hole 122-762C (Table 1). 28 records from (Table 1) Mineralogy and abundance of Truncorotalia tosaensis in ODP Hole 194-1195A. 44501 records from Canadian National Collection (CNC) of Insects, Arachnids and Nematodes. 9858 records from Planktic foraminifera distribution on sediment core GIK17957-2. 16 records from Dinoflagellate cysts of surface sediments. 1 records from Microplankton counts and carbon biomass at station TT007_15-CTD160. 25 records from Phytoplankton abundance at station Sechin_2003-11-25_2, Casma, Peru. 28 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 189-1171D. 504 records from Shellfish (JNHM-MS). 25372 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 143 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 104 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Murcielagos. 221 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 190 records from Colección Paleontológica Invertebrados e Icnologia - CONICET- Argentina. 56051 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 59 records from Biological Records Centre - RISC Non-Native Species Records for Muntjac. 65 records from Occurrence of mammalia relicts at site Vogelherd/Lonetal. 1379 records from Organic-walled dinoflagellate cyst counts of sediment core GeoB9503-5. 11981 records from SMNK Mantid Collection. 161 records from (Table 3) Palynomorph concentrations for ODP Site 105-645. 1380 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 126-790. 91 records from CNIN/Tipos Homoptera. 105 records from Occurrence of mammalia relicts at site l´Abri du Pont d´Ambon. 6264 records from (Table 2) Planktic foraminiferal abundance in Eocene to Oligocene sediments of ODP Hole 177-1090B on the Agulhas Ridge, South Atlantic. 1432 records from Quaternary benthic foraminifera abundance of Hole 95-612. 31 records from Planktic foraminifera assemblage in sediment core GIK17732-1. 1346 records from Percentages of planktonic foraminifera species in sediment core V25-59. 116 records from Occurrence of mammalia relicts at site l´Abri de la Ferrassie. 11 records from Occurrence of mammalia relicts at site Nörre-Lyngby. 260 records from Range table from planktonic foraminifers in ODP Hole 155-930D. 92 records from Siliceous microfossil occurrence, Site 177-1094. 226 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 55 records from Three new species of Ametadoria Townsend (Diptera: Tachinidae) from Area de Conservación Guanacaste, Costa Rica. 569 records from (Appendix D) Benthic foraminifera extinction group species in DSDP Hole 94-608. 237 records from RSPB - Capercaillie national surveys (SCARABBS). 187 records from Taxonomic revision of the Pachycondyla apicalis species complex (Hymenoptera: Formicidae).. 143763 records from University of British Columbia Herbarium (UBC) - Algae Collection. 940 records from Benthic foraminifera abundance of Hole 84-570, Part 2. 227 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 264743 records from ArtenFinder. 9062 records from Northern Biodiversity Program Coleoptera (2010-2011). 609 records from Countryside Council for Wales - Bat Roosts Database- South Wales. 28702 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 1557 records from Hypogean Crustacea recording scheme - Hypogean macro-Crustacea records. 706 records from (Table 1) Benthic foraminifera at DSDP Site 72-516. 8 records from Occurrence of mammalia relicts at site Grotte du Prince. 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 810 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 9948 records from Bees of Canada / Gschwendtner property collection. 14 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 63-125 µm fraction. 72 records from Plasm bearing foraminifera counts of multinet M21/1_MSN603. 33 records from Foraminifera species abundances from tow TT007_2-MOC4. 1 records from Microzooplankton abundance and biomass at station TT050_25-4. 12 records from Distribution of meiobenthos in sediment core M23_134 of the northeastern Atlantic (Table 1). 36845 records from MfN - Fossil invertebrates Ia. 2 records from Nannofossil abundance of Hole 74-526. 855 records from (Table T7) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones Palpha-P3b. 610 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_107MC. 1051 records from Field Study Group of the Dutch Mammal Society (NL) - 2003 - Mammal Survey Alvao Natural Park, Portugal. 45 records from Parcela Permanente en el Pantano Martos. 281250 records from Quadrige. 27264 records from Formidabel; Belgian Ants Database. 1078 records from Fishes of the Congo River 2010 Expedition. 1863 records from Cowan Tetrapod Collection - Herpetology. 75 records from (Table S2b) Nannofossil species richness in the Wilson Lake section. 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 1603 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 374660 records from University of Florida Vertebrate Paleontology. 27 records from New records of Sylvicola (Diptera: Anisopodidae) from Romania. 1965 records from Global caridean shrimp fauna. 54 records from Wiese am Unterbecken. 24 records from New distributional data on ascidian fauna (Tunicata: Ascidiacea) from Mandapam coast, Gulf of Mannar, India. 220546 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 2824 records from Fundación Miguel Lillo - Colección Invertebrados. 464 records from Lepidoptera collection, NTNU, Trondheim. 718 records from HSU Vertebrate Museum Amphibian Collection. 2 records from New distribution records for the rare genus Afrotremex Pasteels (Siricidae: Hymenoptera) and provision of interactive Lucid identification keys to species. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 84 records from BIRDRACE Vogelscheuchen. 89 records from Total foraminifera counts from multinet SO119_MSN1303. 160 records from Total foraminifera counts of multinet M21/2_MSN658. 90 records from Total foraminifera counts of multinet PO231/3_MSN1332. 753 records from Dinoflagellates (organic) in surface sediments of the South Atlantic. 3 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_820-4. 8 records from Abundance of radiolaria at station LV28-29-1. 6 records from Ökosysteme rund um Wedel. 2 records from Smear slide analysis of sediment core GeoB7427-2. 16 records from Nannofossil abundance of Hole 47-398B. 29 records from Composition of the fine silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 104 records from Ross Sea Pycnogonids. 11 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-097BX. 17 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE258. 71 records from (Table 3d) Distribution of planktonic foraminiferal tests in sediments from Core NKA-4T. 3734 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 461 records from Distribución de peces dulceacuícolas introducidos en las cuencas del México central, con especial atención a las localidades dentro del área de distribución de los peces endémicos de la familia Goodeidae. 1004 records from Arctic soft-sediment macrobenthos (EurOBIS). 8 records from Microzooplankton abundance and biomass at station TT045_29-1. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_5-CTD51. 6 records from Microzooplankton abundance and biomass at station NBP97-08-04-5. 48 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 27 records from Benthic foraminifera abundance of Hole 34-320A. 302 records from Range table from benthic foraminifers in ODP Hole 144-874B. 612 records from Range table from benthic foraminifers in ODP Hole 149-900A. 727 records from Range table from benthic foraminifers in ODP Hole 161-975B. 31 records from (Table 3) Oxygen and carbon isotope ratios of Globigerinoides sacculifer of ODP Hole 134-828A. 2117 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 1990 records from Seabird 2000. 4 records from Microzooplankton abundance and biomass at station TT054_24-21. 23 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/042-2. 42619 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 66 records from Range table from ostracoda in ODP Hole 151-910D. 26375 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 366 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 3015 records from Bird specimens in Gifu Prefectural Museum. 342 records from Distribution of planktonic foraminifera in sediment core R657 east of New zealand. 131 records from Artenvielfalt auf dem Schulgelände. 8 records from Occurrence of mammalia relicts at site Wretton. 1549 records from mushroom. 3651 records from Planktic foraminifera abundance of Hole 72-516F. 102 records from Ostracod abundance in sediment core Lz1120. 15016 records from iziko South African Museum - Fish Collection (AfrOBIS). 588 records from Distribution ashore and breeding places of southern elephant seals (OBIS South America, SOUTHERN OCEAN SUB-NODE). 577 records from Marine Benthic Fauna List, Island of Læsø, Denmark. 34506 records from Herbarium de Geo. B. Hinton, México. 106 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Dana Uster. 9858 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 155 records from Bergbaufolgelandschaft am Muldestausee. 124 records from Occurrence of mammalia relicts at site Euerwanger Bühl. 994 records from (Table 6) Quaternary planktonic foraminifers at DSDP Site 65-483. 741 records from Planktic foraminifera abundance of Hole 20-200. 93712 records from Herbarium of Umeå University (UME). 465 records from Range table from planktonic foraminifers in ODP Hole 159-959A. 535 records from Benthic foraminifera abundance of Hole 73-522. 2086 records from RBspirit - Rio de Janeiro Botanical Garden fluid-preserved specimens.. 535 records from Percentages of planktonic foraminifera species in sediment core V30-41. 75 records from Range table from nannofossils in ODP Hole 199-1220A. 264 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 3034 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 71 records from Range table from nannofossils in ODP Hole 199-1215A. 47289 records from Naturalis Biodiversity Center (NL) - Porifera. 1 records from Nouvelles fourmis de l'Imerina oriental (Moramanga etc.).. 2894 records from Insect (SMNH-IN). 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 3082 records from dec2011. 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 64 records from Kabelskebach (Kabelsketal, Saalkreis). 585 records from (Tab. 4) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 11-105, Bahama Lower Continental Rise Hills. 195 records from Phytoplankton abundance in surface water in May 1997, Callao, Peru. 14 records from Collection Pantopoda SMF. 1474 records from Estudios bióticos: Plantas, anfibios, aves y edafofauna epígea en el complejo de páramo Los Picachos. 1 records from Emesopsis infenestra Tatarnic, Wall & Cassis, 2011 (Heteroptera: Reduviidae), genus and species new to New Zealand. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 1447 records from Odonata of the Congo River 2010 expedition. 65535 records from OAC-BIO Herbarium. 5037 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 1000 records from Plant (KOBG_PL). 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 1627 records from The Irish Squirrel Survey 2007. 404 records from Greater Manchester Ecology Unit - Water Vole Distribution for Greater Manchester. 11 records from Etmopterus burgessi sp. nov., a new species of lanternshark (Squaliformes: Etmopteridae) from Taiwan.. 3504 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 1 records from Arthropoden aus südostalpinen Höhlen.. 9123 records from Flora of Słowiński National Park, Poland. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 5116 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 527 records from Inventaire floristique de Beza Mahafaly. 13968 records from NYSM Birds. 19451 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 241 records from BIRDRACE RennVögel Münsterland. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 67 records from Tongrube bei Hettstedt. 57 records from Schulgarten Janusz-Korczak-Realschule. 7950 records from European riparian ground beetles. 2877 records from Flea collection of Slovenian Museum of Natural History (Slovenia only). 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 48 records from Diatom assamblage in samples from sediment trap OG5. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 20 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD88. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 112 records from BIRDRACE Gütersloher Gimpel. 58 records from Plasm bearing foraminifera counts of multinet M12/3_MSN560. 104 records from Total foraminifera counts of multinet M21/6_MSN778. 70 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1387. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD45. 1011 records from Biodiversidad fitoplanctónica de cenotes: Patrones espaciales y temporales. 60 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Steffen Matezki. 1356 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 340 records from Occurrence of mammalia relicts at site Brillenhöhle. 520 records from Planktic foraminifera abundance of Hole 39-357. 1 records from Microfossil abundance of Hole 42-378. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 57 records from Upper Aptian Serre Chaitieu (Niveau Fallot) G. ferreolensis and G. blowi per gram sediment, SE France. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_1-CTD8. 45 records from Wasser-Lernort Nettemündung. 349988 records from BSBI tetrad data for Ireland. 8 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-3. 4100 records from Actualización de la base de datos de crustáceos de la Colección Biológica de la Secretaría de Marina. 64240 records from The Scottish Ornithologists' Club - South East Scotland Tetrad Atlas 1988 - 1994 - non-sensitive breeding species. 3535 records from Colección de Entomología Médica del Instituto Colombiano de Medicina Tropical. 77 records from Total foraminifera counts of multinet PO231/3_MSN1330. 46 records from Foraminifera species abundances from tow TT007_5-MOC9. 3 records from Sarcodine counts and carbon biomass at station TT011_2-CTD21. 17 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/011-3. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 777 records from Planktic foraminifera counts of sediment core RC17-108. 73544 records from Marsh Monitoring Program - Birds. 1833 records from DSMZ Fungi. 11370 records from Distribution of planktic foraminifers of core V22-174. 7 records from Boraginaceae (Cynoglossum cherangauiense). 13702 records from Fundación Miguel Lillo - Colección Ornitológica. 15 records from Herdengelhoehle taxa and datings. 1308 records from Dinoflagellate cysts counts of sediment core MD95-2010. 148 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE293. 300 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part II. 156 records from (4) Assemblages of planktic foraminifera and Sea Surface Temperature (SST) reconstructed from the Modern Analogue Technique in sediment core MD02-2488 during the Last Interglacial. 11054 records from Colección de Sifonápteros del Museo de Zoología "Alfonso L. Herrera", México (MZFC, UNAM). 52 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 11 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR50. 24 records from Occurrence of mammalia relicts at site Overmere. 7 records from Radiolaria assemblage in sediment core GIK23424-3. 2343 records from SMNS Palaeontological collection - Fossil aquatic vertebrates. 19 records from Dinoflagellate abundance of Hole 81-553A. 65 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 44 records from Planktic foraminifera abundance of Hole 19-188. 2083 records from Planktic foraminifera abundance of Hole 72-517. 115 records from Range table from planktonic foraminifers in ODP Hole 155-931C. 389 records from Inventaire National du Patrimoine Naturel : CBN Bailleul. 7 records from Range table from planktonic foraminifers in ODP Hole 192-1185B. 102 records from Benthic foraminifera abundance of Hole 42-372. 157 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 1312 records from (Table 3) Distribution of benthic foraminifers in the > 63 µm fraction in surface sediments from the central Arctic Ocean. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 1 records from Abundance of benthos infauna at station GIK23062-2. 1 records from On the Chilopoda from Turkey. 681 records from (Appendix) Planktonic foraminiferal abundances in ODP Hole 130-805C. 2387 records from The French Collection of Medicago truncatula. 7032 records from EAN - Herbário Jaime Coelho de Moraes. 282 records from CSIRO, Cruise SS199402, Marine Biological Survey, Southeast Australia, 1994. 9933 records from CHAS Mammalogy Collection (Arctos). 69622 records from Fundación Miguel Lillo - Colección Entomológica. 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 147 records from NABU-Auerochsenweide. 100 records from Birdrace-The_Ringers-Friesland. 50 records from Plasm bearing foraminifera counts of multinet SO118_MSN1267. 112 records from Total foraminifera counts of multinet M11/1_MSN526. 51 records from Total foraminifera counts of multinet M21/4_MSN712. 176 records from Total foraminifera counts of multinet M21/2_MSN656. 6659 records from Anfibios y Reptiles del Estado de Tamaulipas, México (UANL). 57 records from Heidesee / Halle. 1 records from Nothrus scaliger. 134 records from Coleoptera identified from the Bellot Street site, Greenwich, London. 1250 records from Colección de Crustáceos Macrobénticos del Golfo de México (ICMyL-DF, UNAM). 438 records from (Table 4) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-709A. 5429 records from Ibaraki Nature Museum, Algae collection. 70704 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1988) (AfrOBIS). 2166 records from Prime Hoverfly (Insecta: Diptera: Syrphidae) Areas (PHA) as a conservation tool in Serbia. 41 records from Revision and phylogeny of the Caribbean weevil genus Apotomoderes Dejean, 1834 (Coleoptera, Curculionidae, Entiminae). 2925 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 11729 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 2 records from Porifera ZMK. 96 records from Birdrace-federleser-Herford. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 63-125 µm fraction. 8 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/046-5. 31 records from Biological data measured on water bottle sampels at station AT_II-119/5_31-7. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_11-CTD137. 212 records from Nanoplankton abundance at station GeoB2017-1. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/091-4. 5 records from Phytoplankton abundance at station Rigel_5_2005-07 in July 2005, Chipana, Chile. 2050 records from Birds (ENHM-BI). 149 records from A multi-proxy investigation of sediment core GeoB7165-1 ~60 km offshore Concepción. 268 records from (Table 5) Relative abundance of benthic foraminifera in ODP Hole 112-686A. 471 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part III. 11 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_236-1. 40 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2215-1. 11431 records from Herp Specimens. 85 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 1634 records from ZFMK DORSA. 180 records from Range table from ostracoda in ODP Hole 144-871A. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/546-2. 349 records from Planktic foraminifera counts of sediment core V20-170. 1000 records from Diplopoda (JJHA-DI). 1537 records from (Table 3) Distribution of planktonic foraminifers in ODP Hole 108-657A. 256 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 116 records from (Table 17) Distribution of planktonic foraminifers in ODP Hole 108-668B. 66 records from Visual Plants (144.41.33.158) - Private collection of Thorsten Kroemer. 28934 records from Coleção de Abelhas do Museu de Ciências e Tecnologia da PUCRS. 485 records from UAM Herpetology Collection (Arctos). 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 222 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment II deployed at station PS64/475-1 during ARK-XIX/3c. 575 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 1733 records from Birds collection of Abiko City Museum of Birds. 171 records from Total foraminifera counts of multinet M42/3_MSN1370. 777 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 23146 records from BC Coastal Waterbird Survey. 35693 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2002) (AfrOBIS). 8684 records from Individual Sightings. 46933 records from Botanical Museum, Copenhagen, Mycology Herbarium. 94474 records from TNHC Herpetology Collection. 808 records from (Table 2) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 113-690C on Maud Rise, Weddell Sea. 294 records from Naturgarten Langenholtensen. 105 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB06 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 172 records from Foraminifera abundance of Hole 59-448A. 1843 records from (Table 3) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583. 84 records from Range table from planktonic foraminifers in ODP Hole 141-859B. 944 records from Range table from planktonic foraminifers in ODP Hole 192-1183A. 498 records from Dinoflagellate abundance of Hole 94-611C. 139 records from Siliceous microfossil occurrence, Site 177-1093. 845 records from Estudio comparativo del zooplancton en dos regiones de México. 355 records from (Table A3) Semi-quantitative frequency of Globorotalia menardii in core SO164-17-2. 72615 records from Marine and Coastal Management - Demersal Surveys (years 1991-1995) (AfrOBIS). 2241402 records from Biologiezentrum Linz. 655 records from Planktic foraminifera assemblage in sediment core GIK17049-6. 3224 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 42 records from Foraminifera abundance of Hole 24-236. 960 records from (Table 11) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-591. 72 records from Range table from benthic foraminifers in ODP Hole 198-1213A. 85 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 736 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 156 records from Colecciones Zoológicas de la Universidad de León, Colección de Malacostráceos. 13595 records from Collection Bryozoa SMF. 14532 records from MVZ Egg and Nest Collection (Arctos). 25 records from A new Gymnotus (Teleostei: Gymnotiformes: Gymnotidae) from the Pantanal Matogrossense of Brazil and adjacent drainages: continued documentation of a cryptic fauna.. 5262 records from Spider Mites Collection of Jean Gutierrez. 21 records from Unveiling of a cryptic Dicranomyia (Idiopyga) from northern Finland using integrative approach (Diptera, Limoniidae). 3 records from Taxonomy of European Damaeidae (Acari: Oribatida) II. Porobelba weigmanni n. sp. (Oribatida, Damaeidae), from East Slovakia, with comments on other known species of the genus. 1 records from Nouvelles fourmis d'Afrique.. 228 records from Herbier Flora selecta exsiccata publié par Ch. MAGNIER (BOUM). 39615 records from Irish vascular plant data 1999-2009. 344 records from (Table T13) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones Palpha-P3b. 41 records from Two new species of Pseudoscopelus (Teleostei: Chiasmodontidae), with a new diagnosis for the genus.. 10 records from A new species and new records of Molophilus Curtis, 1833 (Diptera: Limoniidae) from the Western Palaearctic Region. 6717 records from LSUMZ Mammal Tissues. 163 records from Total foraminifera counts from multinet SO119_MSN1285. 52 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1382. 3900 records from Dinoflagellate cysts counts of sediment core MD95-2042. 32 records from Microzooplankton abundance measured on water bottle samples at station PS65/593-3. 1088 records from (Appendix 2-1) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 7-62A in the western Pacific Ocean. 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 495 records from Field Study Group of the Dutch Mammal Society (NL) - 2013 - Mammal Survey Western Rhodopes, Bulgaria. 1968 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Pinus sylvestris pioneer forest. 14473 records from Entomology at ZMUC, Natural History Musem of Denmark. 1186 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 1998 records from Aves de la cuenca media del río Bogotá. 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 255 records from GENT Lactarius Deliciosi. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 112 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction 63-150 µm. 76 records from Faunal assemblage of sediment core GS7603-10. 479 records from CBS Bacteria Database. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Formicariidae. 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 1 records from Nothrus pollinosus. 20991 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 91 records from BIRDRACE SchrägeVögel. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 64 records from Total foraminifera counts of multinet M42/3_MSN1369. 7457 records from Distribution of dead benthic foraminifera in surface sediments of the Norwegian Sea (Table 3). 11 records from Content of coarse fraction and G. menardii in sediment corev V25-39. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_2-CTD1. 78 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1b. 1278 records from (Appendix 2-6) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 58-445 in the western Pacific Ocean. 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 6 records from Nannofossil abundance of Hole 6-49. 7 records from Nannofossil abundance of Hole 38-336. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/580-2. 591 records from Planktic foraminifera counts of sediment core V16-25. 484 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 117-726A. 2073 records from Bryophyte collection of Jyväskylä University Museum. 145 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE275. 8 records from Phytoplankton abundance at station Rigel_6_2005-03 in March 2005, Chipana, Chile. 135 records from (Table A.08) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (80-150 µm). 1055 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 9 records from Nannofossil abundance of Hole 1-2. 36 records from Nannofossil abundance of Hole 14-141. 1409 records from Planktic foraminifera counts of sediment core AB000280. 2792 records from Birds (UWEP-BI). 13 records from (Table 3) Distribution of some benthic foraminifera in ODP Hole 108-659A. 169 records from Planktic foraminifera counts at CTD station PS55/051. 35 records from Nannofossil abundance of Hole 78-543. 596 records from Planktic foraminifera counts of sediment core A15-558. 2000 records from Shellfish (ASJK_MS). 97 records from (Appendix 5) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2039. 1756 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 6627 records from ATCC Fungi Collection Catalog. 274 records from Herpetological Collection at the Wildlife Institute of India Vertebrate Museum. 173 records from A taxonomic review of the genus Myrmelachista (Hymenoptera: Formicidae) in Costa Rica.. 1298 records from Planktic foraminifera abundance of Hole 23-219. 116 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (75° N section). 29 records from Description of two new species of Hetereleotris (Gobiidae) from the south Pacific, with a revised key to species and synonymization of the genus Pascua with Hetereleotris.. 753 records from Planktic foraminifera counts of sediment core V28-127. 424 records from Bulk components and planktonic foraminifera of sediment core GeoB3375-1. 84 records from Benthic foraminifera abundance of Hole 84-566C. 212930 records from KU Museum of Invertebrate Paleontology. 681 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 1134 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 20 records from (Table 2c) Nannofossil distribution chart of ODP Hole 122-762C. 363 records from Registros de plantas obtenidos en el monitoreo de una de las plataformas instaladas por CORNARE en Antioquia. 168 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2009. 12077 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 5205 records from Botanical Garden Collection. 478 records from EASIANET. 16489 records from AIMS - GBR Nearshore Coral Diversity (OBIS Australia). 82756 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1992) (AfrOBIS). 3161 records from Distribution of foraminifera of sediment core ENAM93-21. 1150 records from Macrozooplankton concentrations estimated from MOCNESS tow samples, Continental Margin Western Antarctic Peninsula, GLOBEC. 1101 records from Relative abundance of ostracods in sediment core Co1202. 19 records from Microplankton data off Mejillones, 2006, Chile. 115 records from (Table 2a) Relative abundance of planktonic foraminiferas in samples of surface sediments and in sediments accumulated about 18 ky ago from typical cores in the area of the Canary upwelling. 132 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 2577 records from Avifauna de la Isla de Cozumel, Quintana Roo_3. 7503 records from Flora del Valle de Tehuacán-Cuicatlán: II Fase. 2184 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 30501 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 1166 records from South Western Pacific Regional OBIS Data Bio Ross Subset (South Western Pac ific OBIS). 36 records from Range table from planktonic foraminifers in ODP Hole 144-877A. 216 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 38 records from Microfossil abundance of Hole 21-206C. 13593 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 98 records from Distribution of palynomorphs in Miocene sediments of ODP Site 188-1165 in the Prydz Bay, East Antarctica (Table 1). 228 records from Occurrence of mammalia relicts at site Grotte Scladina. 371 records from Planktic foraminifera abundance of Hole 63-470. 1 records from Dinoflagellate abundance of Hole 19-183. 8276 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 15 records from Pogonophora collection of National Museum of Nature and Science. 13 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (verified). 7637 records from Mammals Specimens. 8913 records from CRI - Herbário Pe. Dr. Raulino Reitz. 200390 records from Mammalogy Collection - Royal Ontario Museum. 18 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 260 records from Range table from ostracoda in ODP Hole 144-873B. 718087 records from Insect (KNAM-IN). 1794 records from Herbarium BSG Lichenes. 43 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM5. 40 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 10075 records from Nematoda of Costa Rica (INBio). 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 24121 records from Endemic plants of the Congo basin. 2 records from A redescription of Lophostica mauriciana Simon, 1902 (Araneae: Salticidae). 98234 records from CAS Ornithology (ORN). 740584 records from Royal Botanic Garden Edinburgh Herbarium (E). 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Sturnidae. 39 records from Red list project inventory, fungi. 50128 records from Tasmanian Museum and Art Gallery provider for OZCAM. 95 records from Vielfalt verschiedener Wiesen. 28 records from (Table 4) Range chart of calcareous nannofossils from Ross Sea sediment cores. 945 records from (Table 7) Distribution of planktonic foraminifers in ODP Hole 108-660A. 580 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE272. 1092 records from Caracterización y estructura de la ictiofauna de arrecifes rocosos y coralinos en Punta Carrizal, Colima, México para fines de inventario y conservación de la diversidad animal. 50 records from Planktic foraminifera abundance of Hole 60-457. 98229 records from British Lichen Society - BLS Lichen Database: Wales. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 276 records from Environment Agency - Crayfish data update for Environment Agency Thames Region March 2009. 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 76253 records from Irish Vascular Plant Data - Paul Green. 17 records from Hazel Dormouse in Ireland. 6 records from Mammalia (JNHM-MM). 3 records from Blankenfelder See. 33 records from Schüler erforschen die Helme-Aue. 220 records from Assemblage of living benthic foraminifera in sediment core GeoB4917-5. 100 records from Total foraminifera counts of multinet M12/3_MSN536. 50 records from Total foraminifera counts of multinet M21/5_MSN743. 1301 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-159-1. 105 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 1 records from Zetes morticinus. 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 65 records from BIRDRACE Federal Birds of Investigation FBI. 504 records from Schatzinsel Wangerooge. 248 records from Schulgarten der Volksschule. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN743. 318 records from Geometry of coccolith Coccolithus pelagicus in ODP Hole 104-643A. 129 records from Nannofossil abundance of Hole 29-284. 3726 records from (Table 3) Relative abundance of benthic foraminifera in sediment profile HUD84-030-04. 7 records from Appendicularia abundance of station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 2). 85 records from Birdrace-Die_Paradiesvögel-Herford. 43 records from Schulgelände Thurmair-Gymnasium. 29 records from Abundance of Globorotalia menardii of sediment core GeoB2821-1. 147 records from Total foraminifera counts of multinet M10/2_MSN295. 16087 records from RSPB - Corncrake national surveys - territory centres (SCARABBS). 1 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 3468 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-158-1. 45 records from (Table A.09) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (125-250 µm). 12 records from Nannofossil abundance of Hole 20-200. 16 records from Nannofossil abundance of Hole 9-77B. 8 records from Nannofossil abundance of Hole 49-409. 2 records from Range table from nannofossils in ODP Hole 198-1207A. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 22 records from Steinbruch Mainz-Weisenau, 4.Jahr. 26 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 221 records from (Table 1) Abundance of planktonic foraminifera in ODP Hole 113-689B, large size fraction. 85439 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1987) (AfrOBIS). 68081 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1995) (AfrOBIS). 21348 records from Phytopathogenic Fungi Observed by Hans and Hanna Doppelbaur. 8523 records from Distribution of planktic foraminifers of core RC24-16. 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 132 records from Cretaceous ostracods of DSDP Hole 10-95 (Figure 2). 1301 records from Collection Hymenoptera SMF. 2387 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 15000 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 3. 30000 records from Freshwater Fish Specimens of Lake Biwa Museum. 495 records from Life Science National Tsing Hua University. 379 records from Relative abundance of planktonic foraminifera in sediment core MK-325. 239 records from Naturerlebnisraum Koppelsberg. 1 records from Nothrus theleproctus. 186 records from Planktic foraminifera abundance of Hole 94-610. 2730 records from (Table 10) Distribution of planktonic foraminifera in the middle to late Miocene section of ODP Hole 149-900A. 2 records from Range table from planktonic foraminifers in ODP Hole 144-874A. 4085 records from SMNS Palaeontological collection - Tertiary mammals. 540 records from Countryside Council for Wales - CCW Freshwater Fish ad hoc Records for Article 17 Reporting. 2876 records from Naturalis National Natural History Museum (NL) – Mollusca fossils. 79717 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 143 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 63-125 µm fraction. 994 records from Distribution of planktic foraminifera in sediment core GIK23074-1. 7 records from Analyses of the recent components of sediment core PS1219-1. 1458 records from Agentes Bioactivos de Plantas Desérticas de Latinoamérica (ICBG). 1312 records from GEO-Hauptveranstaltung (Insel Vilm). 336 records from Scottish Natural Heritage - Site Condition Monitoring Records from surveys of lamprey species in five river SACs in Scotland. 15 records from Occurrence of mammalia relicts at site Dendermonde. 35 records from Occurrence of mammalia relicts at site Gura Cheii-Rasnov. 5944 records from (Figure 6) Distribution of benthic foraminifers in middle-upper and Quaternary in DSDP Site 71-512. 1380 records from Range table from benthic foraminifers in ODP Hole 189-1168A. 61 records from Range table from benthic foraminifers in ODP Hole 139-857B. 90 records from Collection Ctenophora SMF. 17 records from A review of the genus Pareuchiloglanis (Sisoridae) from the Lancangjiang (upper Mekong River) with descriptions of two new species from Yunnan, China.. 2 records from Eine neue Art der Gattung Suctobelba Paoli (Suctobelba vera n. sp.) aus Deutschland (Acarina: Oribatei). 2064712 records from Museum of Comparative Zoology, Harvard University. 437 records from Chilopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2029 records from National Trust - Sutton Hoo species data held by The National Trust.. 27847 records from Dataset of Passerine bird communities in a mediterranean high mountain (Sierra Nevada, Spain). 350 records from Speothos Venaticus por Guillermo Gil. 5164 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 58 records from Total foraminifera counts of multinet M27/2_MSN882. 22 records from Content of coarse fraction and G. menardii in sediment corev V25-47. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD35. 1607 records from Range table from benthic foraminifers in ODP Hole 162-986D. 63646 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 6 records from (Table 2) Miocene biostratigraphy of the Vierlandian stage in Schleswig-Holstein. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 59 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1388. 5 records from Schulwald Regionale Schule Sprendlingen. 9 records from Coccolith counts of multinet M32/5_MSN982. 775 records from Insect (GNHM-IN). 8063 records from (Appendix B1) Relative abundances of middle Eocene-late Oligocene calcareous nannofossils in ODP Hole 120-748B. 796 records from (Data S1) Palynology of IODP Hole 318-U1356A. 351058 records from Staffordshire Ecological Record - SER Species-based Surveys. 7848 records from Lichen specimen database of Faurie collection. 1421 records from Weevils of Poland. 36188 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 4 records from A new species of Pachyurus Agassiz 1831 (Teleostei: Perciformes: Sciaenidae) from the Río Napo basin, Eastern Ecuador.. 152 records from Nematode abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 60710 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 1 records from Identification of the species of Gnamptogenys Roger in the Americas.. 233 records from Föhrenried (Fronreute und Baindt). 87 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, >125 µm fraction. 1070 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 106 records from Total foraminifera counts of multinet M42/3_MSN1365. 152 records from Abundance of planktic foraminifera at CTD station M39/4_402CTD-55. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_2-CTD16. 9 records from Microzooplankton abundance and biomass at station NBP97-03-04-5. 783 records from Phytoplankton abundance in surface water during cruise CD61. 11 records from Phytoplankton abundance at station Rigel_4_2005-03 in March 2005, Chipana, Chile. 62 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 655 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 70 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 7 records from Nannofossil abundance of Hole 9-82A. 3 records from Nannofossil abundance of Hole 22-212. 15 records from Microfossil abundance of Hole 59-450. 71 records from Distribution of benthic abyssal gastropods in the Iberian Deep-Sea Basin (Table 2). 82 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-699. 2634 records from Mega benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 14 records from (Table 1) Analyses of coarse fraction of DSDP Hole 94-609. 126 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 2610 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Támesis, Antioquia. 7 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 26 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/357-1. 5644 records from (Appendix 1) Planktonic foraminifera abundances in ODP Site 181-1123. 77 records from Occurrence of recent nannoplankton in sediment core M1_MULT242, Arabian Sea (Fig. 2). 7 records from Nannofossil abundance of Hole 5-33. 14 records from Nannofossil abundance of Hole 8-72A. 5 records from Nannofossil abundance of Hole 84-569. 54 records from (Table 3) Distribution of nannofossils in DSDP Hole 87-583A. 4 records from Nannofossil abundance of Hole 52-418. 7991 records from UWBM Herpetology Collection (Arctos). 1129 records from Mollusca Collection of Saitama Museum of Natural History. 2299 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 3 records from Planktic foraminifera abundance of Hole 54-424B. 94 records from Planktic foraminifera abundance of Hole 32-310. 164 records from Planktic foraminifera abundance of Hole 94-610B. 21 records from Hypostomus rhantos (Siluriformes: Loricariidae), a new species from southern Venezuela.. 19 records from Dinoflagellates, pollen and spore abundance of Hole 29-283. 439 records from Antarctic and Subantarctic Asteroid zoogeography (SCAR-MarBIN: Antarctic OBIS). 415 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE206. 240 records from (Table 2) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 123-766A. 593 records from Ostracoda in sediment core PS51/159-10. 500 records from Estudio taxonómico-florístico de la familia Orchidaceae en el Bajío: tribus Epidendrae y Maxillariae. 6987 records from Lyman Entomological Museum. 15886 records from Insect Specimen Database of Fukui City Museum of Natural History. 1796 records from Sea shell specimens database of Mr. Toru Ueda collection, Shizuoka Prefecture Museum of Natural History. 325 records from Planktic foraminifera abundance of Hole 32-305. 135 records from Range table from planktonic foraminifers in ODP Hole 180-1114A. 3130 records from Range table from benthic foraminifers in ODP Hole 154-926A. 15 records from (Table T1) Lithology and palynomorphs of neogene sediments of ODP Hole 178-1095B. 2478 records from (Figure 3) Range charts of selected dinoflagellate cysts in ODP Hole 122-762C. 85 records from Fig 14. Pollen profile from sediment core Schmiecher See. 1293 records from Base de datos y catálogo de helmintos parásitos de anuros de México. 1272 records from Registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 1 records from Akita Prefectural Museum＋Bryozoans Specimens of Akita Prefectural Museum. 21129 records from Pteridophyta specimens of Shizuoka Prefecture Museum of Natural History. 164357 records from The Himalayan Uplands Plant database (HUP Version 1). 41548 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1985) (AfrOBIS). 368 records from Great Lakes Forestry Centre Insect Collection. 19164 records from The Gordon Alexander Orthoptera Collection. 15494 records from (Table 6) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-703A. 907 records from Actualización sistemática y electrónica del acervo de gasterópodos de la Colección Malacológica Dr. Antonio García-Cubas (COMA), del Instituto de Ciencias del Mar y Limnología, UNAM. 251 records from Evaluación del estatus de los géneros Pereskiopsis y Pereskia (Cactaceae) en los Apéndices de la CITES. 900 records from Manual ilustrado de las orquídeas silvestres del estado de Morelos. 77 records from Abundance of dinoflagellates and ciliates at time series station Helgoland Roads, North Sea in 2009. 17374 records from Canadian Museum of Nature Amphibian and Reptile Collection - Anura. 41 records from Altholzparzelle Eilenriede Hannover. 354 records from Foraminifera distribution of sediment core KS310. 24 records from Range table from planktonic foraminifers in ODP Hole 143-865A. 10 records from Range table from planktonic foraminifers in ODP Hole 169-1038A. 387 records from Range table from planktonic foraminifers in ODP Hole 182-1134A. 287 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 5). 187800 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 16 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1024. 486 records from Corales de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMco). 6058 records from Spider (YCEM-SP). 18 records from Redescription of two species of wobbegongs (Chondrichthyes: Orectolobidae) with elevation of Orectolobus halei Whitley 1940 to species level.. 172 records from Redescription of Gymnotus coropinae (Gymnotiformes, Gymnotidae), an often misidentified species of Neotropical electric fish, with notes on natural history and electric signals.. 462 records from Range table from planktonic foraminifers in ODP Hole 155-942A. 122 records from Relative abundance of benthic foraminifera of sediment core GIK13292-3, East Atlantic off Senegal and Gambia (Table 3). 5612 records from Marine Biological Association - 2005-Ongoing United Kingdom MarLIN Shore Thing timed search results. 2509 records from Type Specimen Database of Museum and Institute of Zoology PAS. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 308 records from Wangerooge. 56 records from Estetal (Buxtehude). 15 records from Kühnauer Aue und Kühnauer See. 319 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 103 records from (Table 2) Distribution of living benthic foraminifera in surface sediment of the Elbe estuary. 1 records from Pelops fuligineus. 92 records from The Ants of Bulgaria. 15947 records from Herbarium Erlangense. 1180 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Water Vole Records. 233 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 4761 records from SMDB - Santa Maria Departamento de Biologia. 9 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 3422 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 5043 records from RSPB - Dartford Warbler national surveys in the UK (SCARABBS). 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 56 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-02. 165 records from Total foraminifera counts from multinet M31/3_MSN903. 110 records from Total foraminifera counts of multinet PO247/2_MSN1375. 10046 records from Biological Records Centre - Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 360 records from Order Araneae. 21 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, >150 µm. 233 records from Total foraminifera counts from M35/1_MSN1044. 21 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD13. 2 records from Sarcodine counts and carbon biomass at station TT011_10-CTD123. 15 records from Phytoplankton abundance at station Rigel_4_2005-05 in May 2005, Chipana, Chile. 22 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 14 records from Niphargus dancaui sp. nov. (Amphipoda, Niphargidae) - a new species thriving in sulfidic groundwaters in southeastern Romania. 5841 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coleoptera_Types_Orient. 80 records from BB-Biodiversität b. 149 records from Bayerische Donau - Neu Ulm. 3 records from Nannofossil abundance of Hole 9-80. 35 records from Ortsrand Zandershagen. 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 133 records from Total foraminifera counts of multinet M21/3_MSN676. 2 records from Benthic hard-bottom communities abundance at Lilliguapy in 2010. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_2-CTD26. 32 records from Nannofossil abundance of Hole 67-499. 316 records from Planktic foraminifera counts of sediment core RC11-86. 2210 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 149 records from (Table 2a and b) Median abundances of macrobenthos in surface sediments. 4277 records from Fundación Carl Faust: Herbario del Jardí Botànic Marimurtra: HMIM. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-10-12. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 5265 records from Lower Albian, Niveau Paquier range chart of nannofossils in SE France. 238 records from Coccoliths in ODP Hole 104-643A. 12 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 48 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-703. 703 records from Planktic foraminifera counts of sediment core V25-59. 46 records from Antarctic Isopods. 4 records from Akita Prefectural Museum＋Annelids Specimens of Akita Prefectural Museum. 1374 records from (Table 11) Ranges of benthic foraminifers through the Oligocene in ODP Hole 115-709C. 5 records from A new species of Nanochromis (Teleostei: Cichlidae) from Lake Mai Ndombe, central Congo Basin, Democratic Republic of Congo.. 22 records from Phytoplankton abundance at station Rigel_6_2005-05 in May 2005, Chipana, Chile. 2 records from Nannofossil abundance of Hole 29-280A. 317 records from Planktic foraminifera counts of sediment core RC14-29. 410 records from (Appendix 3) Planktonic foraminiferal composition from ODP Site 172-1056. 8775 records from (Table 2) Occurrences of planktonic foraminifers in samples from ODP Hole 105-647A. 122 records from Review of the ant genus Aenictus (Hymenoptera: Formicidae) in Australia with notes on A. ceylonicus (Mayr).. 143 records from Akita Prefectural Museum＋Malacostracans Specimens of Akita Prefectural Museum. 1656 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 36 records from Occurrence of mammalia relicts at site Trebacki krs. 2827 records from (Figure 5) Distribution of benthic foraminifers in the upper Eocene, Oligocene, and Quaternary of DSDP Hole 71-511. 16 records from A new fungus-growing ant genus, Mycetagroicus gen. nov. with the description of three new species and comments on the monophyly of the Attini (Hymenoptera: Formicidae).. 7311 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 34253 records from MedOBIS (EurOBIS). 1 records from Berlese's Primitive Oribatid Mites. 18192 records from Plant Specimens of The Shimane Nature Museum of Mt. Sanbe. 12 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR72. 97 records from Occurrence of mammalia relicts at site Rejtek 1. 60 records from Planktic foraminifera abundance of Hole 19-192. 96 records from Guadeloupe_manguier. 2 records from DNA barcoding reveals a new record of Potamogeton distinctus (Potamogetonaceae) and its natural hybrids, P. distinctus × P. nodosus and P. distinctus × P. wrightii (P. ×malainoides) from Myanmar. 6 records from Across the Baltic: a new record for an enigmatic black scavenger fly, Zuskamira inexpectata (Pont, 1987) (Sepsidae) in Finland. 2074 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Aves. 675 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1400-4. 353 records from Stadtgebiet (Dannenberg). 16 records from Abundance of radiolaria at station LV28-3-3. 2238 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 7 records from Range table from planktonic foraminifers in ODP Hole 182-1132A. 34341 records from Historical hyperbenthos data (1987-2001) from the North Sea and some adjacent areas (EurOBIS). 324 records from (Appendix B) Planktic foraminiferal assemblages from ODP Holes 113-689B and 113-690B. 1597 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Historico_cofc). Facultad de Ciencias. Universidad de Córdoba. 4244 records from Insect Specimens of Lake Biwa Museum. 29 records from Occurrence of mammalia relicts at site la Grotte du Thai. 3653 records from A Dataset of Deep-Sea Fishes Surveyed by Research Vessels in the Waters around Taiwan. 226 records from Range table from benthic foraminifers in ODP Hole 182-1130A. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 24 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171C. 816 records from Phytoplankton abundance in surface water in February 1998, Ilo, Peru. 230221 records from UA Herbarium. 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 240 records from Range table from nannofossils in ODP Hole 199-1219A. 21261 records from Sukkulentensammlung Zürich. 2199 records from Plantlife International - Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 1 records from H. Sauter's Formosa-Ausbeute: Formicidae (Hym.).. 300 records from A systematic revision of the genus Archocentrus (Perciformes: Cichlidae), with the description of two new genera and six new species.. 1 records from Nothrus posticus. 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 1020 records from Irish Marine Turtle Database. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 1489 records from Herbarium Rhoenmuseum Fladungen. 89 records from Birdrace-Team_Wangerooge-Friesland. 40 records from Tiere und Pflanzen um uns herum !. 135 records from Waldi-Weiher. 5 records from Fledermäuse u. nachtaktive Insekten. 269 records from BIRDRACE Dithmarscher Deichhühner. 100 records from Grenzturm Hohen Neuendorf. 28 records from Stadtpark Prinzengarten (Sigmaringen). 110 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 130 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607. 122 records from Phytoplankton abundance at station CD46_1005C#4. 11 records from Benthic macrofauna abundance of sediment core 13077-087. 2863 records from Invertebrates compiled by W.Block. 525 records from Benthic foraminifera abundance of Hole 40-360. 1636 records from Biodiversity of Antarctic Zoobenthos (SCAR-MarBIN: Antarctic OBIS). 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 4888 records from (Table 1) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Hole 79-545. 1 records from Nothrus pulverulentus. 133 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Parulidae. 637 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 2480 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 19127 records from Biological Records Centre - Cerambycidae Dataset. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 180 records from Paul-Gerhardt-Schule Dassel. 86 records from Plasm bearing foraminifera counts from M35/1_MSN1061. 781 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 21 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, >150 µm. 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 46 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/427-6. 6 records from Microzooplankton abundance and biomass at station NBP97-08-28-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 185 records from Abundance of coccosphere-units of site GIK23414. 31 records from Nannofossil abundance of Hole 4-23. 16 records from Lepidurus arcticus survey Northeast Greenland 2013. 49 records from (Appendix 1) DSDP Site 94-607A ostracode species census data. 23 records from Landwehrbach. 20 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 34 records from sediments composition of surface sediment samples Men4377-7 to Men4418-1. 112 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2009. 692 records from Collection Trilobita SMF. 581051 records from Swiss National Butterflies Databank. 1236 records from Percentages of planktonic foraminifera species in sediment core V30-40. 18 records from Plasm bearing foraminifera counts from multinet M31/2_MSN897. 73 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1376. 3 records from Sarcodine counts and carbon biomass at station TT011_15-CTD168. 7 records from The interstitial subsoil fauna of the upper beach level at Sarso Beach, Red Sea (Table 2). 482 records from Kühmark bei Wetzlar. 2 records from Nannofossil abundance of Hole 7-64A. 9 records from Diatom abundance measured on water bottle samples at station PS58/038-3. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-020. 85 records from Sedimentological investigation on core V25-45. 10 records from Microzooplankton abundance and biomass at station TT043_21-22. 3224 records from (Appendix C) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748B. 175 records from Neißetal. 1097 records from (App 4) Relative contents of benthic foraminifera species in Holocene sediments from Core BP00-07/05. 1148 records from (Table 4) Planktonic foraminifers from ODP Hole 114-704B. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 49 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Amphipods. 1386 records from Red list project inventory, lichens. 2 records from List of the specimens of dipterous insects in the collection of the British Museum. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 152 records from Range table from planktonic foraminifers in ODP Hole 177-1088B. 12 records from A new species and new records of Hentzia (Araneae: Salticidae: Dendryphantinae) from the United States. 234 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 2. 22033 records from CUMV Mammal Collection (Arctos). 48 records from Benthic foraminifera abundance of Hole 42-380A. 892 records from Weevils of Wales and England. 1208 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1125. 7 records from Megafauna biomass in surface sediment during cruise PLG95A. 6 records from Una nuova specie di Eupolybothrus della fauna di Grecia (Chilopoda, Lithobiomorpha). 358 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of IODP Hole 318-U1356A. 203 records from Planktic foraminifera abundance of Hole 72-515B. 2274 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 707 records from Benthic foraminiferal assemblages of Upper Cretaceous sediments from DSDP Hole 74-527 in the Angola Basin, South Atlantic Ocean (Table I, Appendix II). 83 records from Abundance of birds on the channels of Lena Delta in the brood period. 691 records from RSPB - Black grouse national surveys (SCARABBS). 2896 records from Localizaciones satélite de un ejemplar ("Lorien") de águila azor perdicera (Aquila fasciata Vieillot, 1822) en Aragón. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 1402 records from Free-living marine Nematodes from Puerto Madryn and Pozo sandy beaches (Chubut, Argentina), 2006.. 1 records from Cheiloneurus flaccus (Walker, 1847) (Hymenoptera: Encyrtidae), new to New Zealand. 20043 records from Mollusca collection of National Museum of Nature and Science. 188781 records from Reptiles and Amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 2654 records from Collection of Hymenoptera. 223320 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 10744 records from RSPB - Bringing Reedbeds to Life Invertebrate Survey of three key reedbed sites in England in 2009, 2010. RSPB led project with 50% funding from Natural Engl. 47 records from Taxonomic status of the Guadalupe Darter, Percina apristis (Teleostei: Percidae).. 9 records from Diaphoromyrma, a new myrmicine ant genus (Hymenoptera: Formicidae) from North Eastern Brazil. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 8629 records from National Taiwan University. 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_8-CTD102. 6 records from Microzooplankton abundance and biomass at station NBP97-08-19-1. 6887 records from (Figure 13) Distribution of middle Miocene through middle Pleistocene planktonic foraminifera in ODP Hole 132-810C. 19984 records from HRCB - Herbário Rioclarense. 4689 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 60 records from Schafsweide Seniorenhaus Berghof. 12 records from Art´n Vielfalt im Kinderwald. 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 198 records from Total foraminifera counts from M35/1_MSN1047. 1 records from Celaeno detrita. 81 records from Foraminifera species abundances from tow TT011_6-MOC65. 1683 records from (Appendix 2) Distribution of planktonic foraminifera in the last 70 kyr of sediment core MD95-2043 from the western Mediterranean Sea. 6 records from Microplankton counts and carbon biomass at station TT012_5-CTD35. 7 records from Distribution of meiobenthos in sediment core M23_199 (2) of the northeastern Atlantic (Table 1). 483 records from Artenvielfalt im Rhein-Neckar-Raum. 127226 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 1 records from Nothrus bicarinatus. 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 7551636 records from BirdLife Australia, Birdata. 181 records from Alien Species in Poland - Animals. 1 records from Papilio Sticheli nov. spec. aut subsp.. 2 records from Oribatids from Switzerland VII (Acari: Oribatida: Mycobatidae 1) (Acarologica Genavensia XCIX). 102 records from Birdrace-OAG_Neuwerk-Hamburg. 61 records from BIRDRACE Baumläufer. 76 records from BIRDRACE Nachtigallen. 149 records from Plasm bearing foraminifera counts from M35/1_MSN1046. 84 records from Anisopodidae and Thaumaleidae (Diptera: Nematocera) of Ireland. 10 records from Zoobenthos in surface sediments during Professor Vodyanitskiy cruise PV32. 7346 records from MfN - Fossil vertebrates III. 4 records from Nannofossil abundance of Hole 16-156. 20 records from Nannofossil abundance of Hole 7-63A. 210 records from RSPB - Black grouse lek survey in the Scottish Borders, 2010 (Southern Upland Partnership). 15 records from Abundance and composition of meiobenthos in surface sediments at Fladen Ground stations in August 1975, North Sea (Table 4). 69 records from Mönchspark. 92 records from Nannofossil abundance of Hole 31-296. 7 records from Nannofossil abundance of Hole 27-259. 19 records from (Table 1) Planktonic foraminifer abundance and stable isotope ratios of a sediment core near Baddeckenstedt, north Germany. 15675 records from Institut Botanic de Barcelona, BC-Histórico. 1046 records from (Appendix Table 4) Number of planktonic foraminiferal specimens within species in Late Creatceous sediments of ODP Hole 122-763B from the Exmouth Plateau, eastern Indian Ocean. 2630 records from Planktic foraminifera abundance of Hole 68-502A. 313 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_93MC. 290 records from The symphytognathoid spiders of the Gaoligongshan, Yunnan, China (Araneae: Araneoidea): Systematics and diversity of micro-orbweavers. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 61 records from Rotes Steigle (Panzerübungplatz Böblingen). 54 records from Biotope im Schulumfeld. 39 records from Calcareous dinocysts along profile Ruegen. 608 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 90-594. 72 records from (Table 5) Distribution of nannofossils in DSDP Hole 87-583F. 14 records from Nannofossil abundance of Hole 14-140. 10 records from Benthic macrofauna abundance of sediment core 12930-059. 797 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV23. 5634 records from CeDoc de Biodiversitat Vegetal: BCN-Phycophyta. 112 records from Landschaftsschutzgebiet Hexenberg (Erftstadt-Erp). 106 records from Arteninventar rund um den Rannahof. 4 records from Range table from nannofossils in ODP Hole 139-857A. 90 records from Planktic foraminifera counts of sediment core RC13-158. 704 records from Planktic foraminifera counts of sediment core V18-207. 33403 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 31 records from Bayerische Donau - Tapfheim. 1212 records from RMT Trawl catch from the 1990/91 V6 AAMBER2 voyage. 501 records from EcoRecord - Mayfly (Ephemeroptera) records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 296 records from (Appendix 1c) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber from MIS 11 of sediment core GeoTu_SL096. 42 records from Chaetognatha - SMF. 27 records from Pollen data of trap CB3. 1404 records from (Table 1) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-762C, Part III. 5 records from A Redescription of Conoppia palmicinctum (Michael, 1880) (Acari, Cryptostigmata). 941 records from Pteridophyta specimens of Iwate Prefectural Museum. 7 records from Phytoplankton abundance measured on water bottle samples at station PS65/466-2. 63 records from Planktic foraminifera counts of sediment core V19-21. 8336 records from Birds (GMBO-BI). 1148 records from Southern Ocean Ostracoda (except Halocypridina). 249 records from (Table 1) Relative abundance of selected benthic foraminifera in ODP Hole 104-644A. 21 records from (Figure 6) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-540. 429 records from Larval fish at Helgoland Roads in 2004. 1159 records from Countryside Council for Wales - Bat Roosts Database - North East Wales. 906 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Fitoplancton. 299 records from Korean Insect Database (Hymenoptera: Ichneumonidae). 11831 records from UCM Bird Collection (Arctos). 20 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area II. 91 records from Range table from benthic foraminifers in ODP Hole 188-1165B. 124 records from Range table from benthic foraminifers in ODP Hole 189-1171A. 195 records from New synonymy, new species, new keys to Neivamyrmex army ants of the United States.. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Procellariidae. 94 records from (Table 1) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Sea of Okhotsk side). 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 35548 records from Herpetology. 122 records from Kelp rafts in the Southern Ocean (Australian Antarctic Data Centre). 49 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 191 records from Foraminifera abundance of sediment core C1960.202. 5 records from Analyses of the recent components of sediment core PS1216-1. 27 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB01 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 1 records from Occurrence of mammalia relicts at site Ejstrup. 1 records from Oribates ovalis. 303033 records from Natural History Museum, University of Tartu. 1963 records from Range table from planktonic foraminifers in ODP Hole 157-953C. 35 records from Range table from planktonic foraminifers in ODP Hole 180-1112A. 10 records from Oberservation of birds at station PS14/143 along 49° West. 181 records from Nematode abundance of the Eastern Mediterranean Sea in cold seep sediments collected during MSM13/3 and MSM 13/4 cruises (2009). 786 records from Planktic foraminifera abundance of Hole 72-518. 468 records from Range table from planktonic foraminifers in ODP Hole 155-932A. 93 records from Range table from planktonic foraminifers in ODP Hole 180-1111A. 3466 records from (Table 3) Distribution of benthic foraminifers at DSDP Hole 21-206. 288 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 6 records from (Table 1) Dinoflagellate cyst zonations at ODP Site 202-1233. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 10 records from (Figure 9) Relative abundance of nannoliths at DSDP Hole 62-465A. 1661 records from Arácnidos de Centroamérica. 23 records from (Table 3) Neogene relative abundances of Uvigerina spp. at DSDP Hole 95-613. 1197 records from Hertfordshire Biological Records Centre - Hertfordshire Urban Surveys (incomplete). 41 records from Nine genera of Eucnemidae (Coleoptera) new to Peru, with a key to Peruvian genera. 87143 records from Sheffield Bird Study Group - Sheffield Bird Study Group (Yorkshire records). 15 records from Urwald 2 (Bad Waldsee). 226 records from (Table A1) Annual biomass of plants and animals recorded on Bylot Island between 1993-2009. 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 111802 records from Highland Biological Recording Group - HBRG Insects Dataset. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 873 records from Kartlegging av spredning av fremmede bartrær. 337 records from One century of vegetation change on Isla Persa, a nunatak in the Bernina massif in the Swiss Alps. 89 records from Devon Biodiversity Records Centre - Devon Himalayan balsam data 1997 to 2007. 1 records from A new species of Enoplomischus from Kenya (Araneae: Salticidae: Leptorchestinae). 38 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto75-83. 62099 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 56 records from Zitadelle Berlin-Spandau (7b). 232 records from Distribution of planktic foraminifera of sediment trap OG5. 234 records from Size of planktic foraminifera at CTD station M39/4_352CTD-11. 7929 records from Dinoflagellate cysts in surface sediments. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 57 records from Schulgarten Fichteschule. 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 59 records from Schulteich Freie Waldorfschule Darmstadt. 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 159 records from Total foraminifera counts of multinet SO118_MSN1251. 44 records from Total foraminifera counts of multinet M27/2_MSN879. 18750 records from National Trust - Hatfield Forest species data held by The National Trust.. 13 records from Distribution of meiobenthos in sediment core M23_203 of the northeastern Atlantic (Table 1). 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 27 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5121-1. 18 records from Smear slide analysis on sediment core GeoB4206-1. 12 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/092-3. 327 records from Foraminifera abundance of Hole 58-443. 751 records from Planktic foraminifera abundance of Hole 49-408. 349 records from Range table from planktonic foraminifers in ODP Hole 182-1126B. 1764 records from Arachnida of Costa Rica (INBio). 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN658. 195 records from (Table T2) Concentrations and accumulation rates of Globorotalia menardii at ODP Hole 175-1087A. 137 records from Planktic foraminifera counts at CTD station PS55/077-1. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-17-7. 3 records from Sarcodine counts and carbon biomass at station TT011_9-CTD115. 22 records from Phytoplankton abundance at bottle station GOM1/6. 14 records from Occurrence of recent nannoplankton in surface sediments at M1_MULT243, Arabian Sea (Fig. 2). 12 records from Nannofossil abundance of Hole 74-528A. 4 records from Nannofossil abundance of Hole 55-430A. 57 records from Kindervilla Aussengelände/ Hiltroper Park. 410 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part II. 492 records from Pliocene/Pleistocene benthic foraminiferal abundances from hole KR9912PC4. 19 records from Pollen record from Mamontovy Klyk. 107 records from Bases de datos de Poliquetos pelágicos del Golfo de México y Mar Caribe mexicano. 651 records from Range table from planktonic foraminifers in ODP Hole 155-940A. 171 records from Sahrbachtal Kreis Ahrweiler. 2 records from Nannofossil abundance of Hole 18-174A. 22 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI237. 13 records from Benthic macrofauna abundance of sediment core 12930-065. 264 records from Planktic foraminifera counts of sediment core RC12-339. 137 records from Planktic foraminifera counts of sediment core V28-25. 3527 records from Inventario florístico y base de datos de la Reserva Ecológica Sierra de San Juan, Nayarit, México. 479 records from Granulometry and foraminiferal content of sediment core PI-88-AR_P5. 1654 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-4. 10 records from UC Davis Department of Anthropology Museum. 79 records from Umgebung von Schorndorf. 1059 records from Planktic foraminifera abundance of Hole 15-148. 3953 records from Colección de Ostrácodos Recientes del Sur del Golfo de México (ICMyL-DF, UNAM). 91 records from Genética y taxonomía de los robalos (Centropomus spp) del golfo de California, México. 13 records from Foraminifera abundance of Hole 57-438B. 710 records from Range table from benthic foraminifers in ODP Hole 172-1054A. 1 records from Nothrus doliaris. 173 records from (Table T3) Stable isotope ratios and abundances of foraminifera from ODP Hole 172-1063D. 2 records from Enchelycore nycturanus, a new moray eel from South Africa (Teleostei: Anguilliformes: Muraenidae).. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 µm fraction. 18 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT012_5-CTD85. 2320 records from (Table 7) Distribution of planktonic foraminifera in the early Miocene to late Pliocene section of ODP Hole 149-899A. 5 records from Description of lithologic section units of IODP Hole 325-M0046A. 23 records from AlgaTerraMovies. 804 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 19 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-139BX. 465 records from Philosophenwald und Wieseckaue in Gießen. 376 records from Wupperaue bei Kemna (Wuppertal). 145 records from Microplankton abundance in the euphotic zone of the Levantine Sea in October-November 1991. 1225 records from (Table T5) Benthic foraminifer occurrence in ODP Hole 183-1139A sediments. 23 records from Benthic foraminifera abundance of Hole 93-603. 4714 records from Colección de Anfibios. 19 records from MVZ Herp Observations (Arctos). 45899 records from UFP - Herbário UFP - Geraldo Mariz. 2577 records from Shellfish (WSHN-MS). 2708 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1218A and 199-1219A sediments. 153 records from Landschaftsschutzgebiet "Holmer Sandberge". 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 8462 records from Polish seed gene bank – historical passport data of accessions. 37 records from Content of coarse fraction and G. menardii in sediment corev V16-202. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 4 records from Zwischen Enz und Schule. 521 records from Bayerische Donau - Leipheim. 12337 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 2 records from Nannofossil abundance of Hole 10-87. 62 records from Range table from benthic foraminifers in ODP Hole 174-1071C. 3 records from Dinoflagellate abundance of Hole 85-572. 1457 records from Collection Paläobotanik SMB. 5 records from New records of Paraleptophlebia werneri Ulmer, 1920 and P. strandii (Eaton, 1901) from Finland (Ephemeroptera, Leptophlebiidae). 3096 records from Biological Records Centre - Mosquito Recording Scheme. 185 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Tinamidae. 1167 records from Bird. 68939 records from European Invertebrate Survey (EIS-NL) - Orthoptera Observations. 731 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 5962 records from Broadland Environmental Services Limited - Reptile distribution within Broadland (2004-2011): based upon field signs and sightings. 28 records from (Table A) Wet weight night biomass of dominant mesozooplankton groups obtained from night catches within the Bismark Polygon in June 2001 and June-August 2002. 17 records from Coccoliths in sediment core PS1527-2. 2513 records from Carabidae of the Tatra Mts.. 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 1659 records from MISE Project Waterford Otter Records, 2011-2015. 299 records from (Tables 1-15) Morphometric characteristics of the genus Hinia (Nassariidae, Gastropoda) in the Tertiary of northwest Germany. 84 records from BIRDRACE Avinauten. 95 records from Total foraminifera counts from multinet M31/2_MSN896. 160 records from Total foraminifera counts of multinet M21/1_MSN607. 43 records from (Table 5) Distribution of calcareous nannofossils in DSDP Holes 92-600C and 92-601. 63 records from Microzooplankton abundance measured on water bottle samples at station PS58/108-1. 44 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-49. 526 records from (Table 1) Relative abundances of calcareous nannofossils in ODP Hole 115-711A. 1161 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 4240 records from Herpetology Collection. 73 records from Tiergarten (Zeitz). 37 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100800. 347 records from Planktic foraminifera abundance of Hole 21-209. 876 records from Range table from planktonic foraminifers in ODP Hole 138-847B. 9420 records from Sussex Biodiversity Record Centre - Sussex Bryophyte Atlas Data edited by Howard Matcham. 1120 records from Field Study Group of the Dutch Mammal Society (NL) - 2007 - Mammal Survey Estonia. 107 records from Hypogean Crustacea of Ireland. 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 10 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 3560 records from Recuento de la diversidad florística de Veracruz. 2814 records from Anfibios y reptiles del estado de Querétaro. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR16. 1 records from Occurrence of mammalia relicts at site Egtved. 1017 records from Planktic foraminifera abundance of Hole 26-253. 500 records from Foraminifera abundance of Hole 48-404. 59 records from Range table from planktonic foraminifers in ODP Hole 180-1116A. 3788 records from Faun. 1 records from Nothrus sordidus. 1 records from Deux especes nouvelles pour la science du genre Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). - Two new species for the science in the genus Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 130 records from Planktic foraminifera counts of sediment core RC11-120. 983 records from (Table 2) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-747A. 976 records from Mammals (NSMK-MM). 6149 records from Hongos del estado de Veracruz. 236 records from Los peces del área oaxaqueña de la Reserva de la Biosfera Tehuacán-Cuicatlán. 2000 records from Biodiversidad de los crustáceos dulceacuícolas del centro de Nuevo León y noroeste de Tamaulipas. 661 records from Ictiofauna de la Bahía de Banderas Nayarit, Jalisco y zonas adyacentes, México. 163562 records from Bird specimens. 41915 records from Composition of planktonic foraminifera species in 1123 surface sediment samples compared with sea surface temperatures from the Levitus Atlas. 70 records from (Table 4) Coiling direction changes of Neogloboquadrina acostaensis during the latest Miocene and early Pliocene of DSDP Hole 94-608 from the North Atlantic Ocean. 3 records from Planktic foraminifera abundance of Hole 54-419. 3 records from Sarcodine counts and carbon biomass at station TT007_3-CTD29. 73 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Anhimidae. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-078. 1013 records from Planktic foraminifera counts of sediment core RE5-034. 18 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683A, Part I. 185 records from (Table 2) Abundances of dinoflagellates in ODP Hole 105-646B. 14 records from Description of lithologic section units of IODP Hole 325-M0047A. 21248 records from Birds Specimens. 2960 records from Herp specimens. 36992 records from Vascular Plants Collection of Sagamihara City Museum. 638 records from Geochemistry and sedimentology on core PO200/10_21-1. 1371 records from Planktic foraminifera assemblage in sediment core GIK16773-1. 321 records from Fuldaaue (Stadtgebiet Fulda). 5 records from Occurrence of mammalia relicts at site Victoria Cave. 234 records from Occurrence of mammalia relicts at site Pestera Cioarei. 6219 records from Specimens of G. Fenoul Herbarium (FEN). 144 records from Whale Observations from the British, Australian and New Zealand Antarctic Research Expedition (BANZARE) voyages 1929-30 and 1930-31. 8 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 2940 records from The Erysiphales Collection at the University Halle-Wittenberg. 5 records from Range table from planktonic foraminifers in ODP Hole 178-1103A. 284968 records from Balfour-Browne Club - Water Beetle Surveys from Britain and Ireland. 3763 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 1636 records from Diptera, NEF. 778 records from Gloucestershire Centre for Environmental Records - Gloucestershire BAP Priority Species: Great crested newts. 89 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 5 records from Arthropoden aus südostalpinen Höhlen.. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 3669 records from ARKO strandeng. 3027 records from Fungi Collection in BCRC. 88 records from (Figure 5) Distribution and relative abundances of microbiota recovered from the Jurassic section of DSDP Hole 79-547B. 766 records from Reptiles and Amphibians Distribution Atlas 1978 (An Foras Forbartha). 52 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Casilda (Luna & Piazza, octubre 1999). 139 records from Inventario de Aves en la Finca la Reserva, Yopal, Casanare. 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 13577 records from JOI - Herbário Joinvillea. 36 records from Two new species of Isbrueckerichthys Derijst, 1996 (Siluriformes: Loricariidae) from the rio Paranapanema basin, Brazil.. 3 records from First record of the genus Leptanilloides (Hymenoptera: Formicidae: Dorylinae) from the United States. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 9 records from Phytoplankton abundance at station Casma_2003-06-04_2, Casma, Peru. 190 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 6 records from Histoire naturelle des Hymenopteres. Deuxieme partie: Les Formicides.. 99 records from IWDG Ship Surveys Sightings - Heritage Council Surveys 2004. 3769 records from Eggs Specimen. 2 records from Nannofossil abundance of Hole 66-488. 8 records from Component analysis of TV-guided grab sampler GeoB10071-4. 6723 records from NOAA HML Tidal Creek Database. 51 records from Taxonomic revision of the spider family Penestomidae (Araneae, Entelegynae). 5152 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 4745 records from Collection botanique Le Grand A. (BOUM). 65 records from Abundance of living benthic foraminifera in sediment core CD86_05_BC5. 33 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 3. 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55803#5, >150 µm. 49 records from Total foraminifera counts of multinet FCA97C_MSN1345. 94 records from Total foraminifera counts of multinet M21/4_MSN697. 115 records from Total foraminifera counts of multinet PO247/2_MSN1382. 88 records from Total foraminifera counts of trap L2_92_A43. 383 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 103 records from Birdrace-Die_Nachtigallen-Herford. 40 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, 63-150 µm. 80 records from Total foraminifera counts of multinet M12/3_MSN543. 90 records from Plasm bearing foraminifera counts of multinet M21/2_MSN639. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_240-4. 9955 records from Benthic foraminifera abundance in counts of Hole PRAD1-2. 1360 records from (Appendix table DR1) Foraminiferal distribution data for ODP Hole 178-1098B. 121 records from Relative abundance of radiolaria in surface sediments. 72 records from Occurrence of nannoplankton observed in Early Pliocene samples from Zanclean stratotype of Capo Rossello, Sicily (Table I). 6 records from (Table 1) Lipid and organochlorine content in blood of common eiders (Somateria mollissima) in Svalbard. 12 records from Distribution of meiobenthos in sediment core M19_229-2 of the northeastern Atlantic (Table 1). 279 records from Koleopterologen am Bausenberg. 34 records from Relative abundance of coccosphere-units of sediment core GIK23071-3. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_8-CTD102. 2 records from Nannofossil abundance of Hole 74-525A. 262 records from Coiling ratios of Pulleniatina spp. in sediments from DSDP Hole 16-157. 214 records from Planktic foraminifera counts of sediment core V27-86. 142 records from Ostracoda in sediment core PS51/135-4. 140 records from Corvids Literature Database. 1848 records from (Table 3) Occurrences of planktonic foraminifers in samples from ODP Hole 105-647A. 884 records from Percentages of planktonic foraminifera species in sediment core EN066-10PG. 24 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB02 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 1137 records from Planktic foraminifera abundance of Hole 72-516F. 172 records from Range table from planktonic foraminifers in ODP Hole 141-863B. 97 records from Range table from planktonic foraminifers in ODP Hole 182-1133B. 400 records from Distribution of planktonic foraminifera in Oligocene-Miocene of three drill sites from the netherlands Peel area. 8967 records from National Invasive Species Database. 618 records from RSPB - Scottish Crossbill National Survey in the UK in 2008 (SCARABBS). 325 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 115-708A. 3440 records from Actualización de la base de datos del proyecto H278 Apoidea (Hymenoptera) del Valle de Zapotitlán de las Salinas, Puebla. 323 records from CNAN/Pseudoscorpiones. 221 records from Foraminifera abundance of sediment core IN68-5. 628 records from Relative abundance of planktic foraminifera in sediment core TR126-29 from the 120 kyr time slice reconstruction. 55747 records from Colección de Referencia de Lepidópteros Diurnos Mexicanos de la CNIN (Lepidoptera: Papilionoidea) (IBUNAM). 101 records from Schulgelände IGS-Frosch (Thaleischweiler-Fröschen). 81 records from GEO-Tag der Artenvielfalt auf dem Bausenberg mit den 4. Klassen der Brohltaler Grundschulen. 3027 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 2 records from Occurrence of mammalia relicts at site Condover. 6229 records from (Table 9) Percentages of planktonic foraminiferal taxa from Site GIK17940. 21 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-112BX. 80846 records from Colección de Lepidópteros del Museo de Zoología 'Alfonso L. Herrera', México (MZFC, UNAM). 354 records from Microfossil abundance of Hole 35-323. 72 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 20394 records from R. L. McGregor Herbarium Lichen Collection. 14882 records from NCSM Mammals Collection. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 326 records from Colección nacional de palmas de Colombia - JBQ. 11518 records from Merseyside BioBank - North Merseyside Insects (verified). 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, >125 µm fraction. 448 records from Geometry of coccolith Gephyrocapsa in sediment core GIK23062-1. 8 records from Nannofossil abundance of Hole 49-412A. 50 records from Flora und Fauna im Brexbachtal. 9 records from Akita Prefectural Museum＋Cephalaspidomorphs Specimens of Akita Prefectural Museum. 15718 records from Universität Salzburg. 262 records from Planktic foraminifera abundance of Hole 1-3. 86 records from (Table 9) Planktonic foraminifer abundance of ODP Site 162-985. 2 records from Neobythitoides serratus, a new bathyal genus and species from the East China Sea (Teleostei, Ophidiidae).. 175 records from NPWS Pine Marten database. 10 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB6. 35 records from Range table from planktonic foraminifers in ODP Hole 144-873A. 11 records from Oberservation of birds at station PS14/145 along 49° West. 1 records from Nothrus echinatus. 18107 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 4685 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2006. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 94 records from Total foraminifera counts of multinet PO231/3_MSN1333. 17355 records from Ibaraki Nature Museum,Lichen collection. 14 records from Range table from benthic foraminifers in ODP Hole 178-1101A. 1 records from Damaeus nodipes. 540 records from (Appendix 3) Abundances of benthic forminifera in DSDP Hole 74-525A. 69 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Vireonidae. 1440 records from Museum TwentseWelle (NL) - Fossil Ammonites Collection. 179 records from Seven new species of the Neotropical electric fish Gymnotus (Teleostei, Gymnotiformes) with a redescription of G. carapo (Linnaeus).. 40 records from (Table T1) Kerogen and organic constituents in ODP Hole 183-1138A, Kerguelen Plateau. 3939 records from Census of plant species in Pahou forest reserve. 3 records from On the centipedes (Chilopoda) of the Republic of Macedonia. 2205 records from BoGART. 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 558 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 90 records from University of Amsterdam (NL) - Páramo Vegetation Research, paramo in the Sabana de Bogota area, Colombia. 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 1641 records from NCSM PaleoBotany Collection. 20957 records from CHAS Herpetology. 23 records from First record of the genus Venanus (Hymenoptera: Braconidae: Microgastrinae) in Mesoamerica, with the description of two new species from Costa Rica. 39 records from ECOCEAN MantaMatcher. 7356 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Moss and Liverwort Observation Records. Pre-2010 for Cumbria. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 9871 records from Dumfries and Galloway Environmental Resources Centre - Micro-moths distribution for Dumfries and Galloway. 6 records from Fließgewässeruntersuchung am Haselbach. 158355 records from All Ireland Non-Marine Molluscan Database. 194 records from Bodenteicher Seewiesen. 4956 records from NRM-Herpetology. 101 records from Assemblage of total living benthic foraminifera in sediment core SO119_MC501. 4 records from Kleinod unter Hochspannung. 4251 records from Aves de la cuenca media del río Chambery, Caldas. 12 records from Microplankton abundance at bottle station SEPT-1999-K7. 230 records from Range table from benthic foraminifera in ODP Hole 199-1220B. 2568 records from Fish (NHMK-PI). 589 records from (Table 12) Distribution of benthic foraminifera in bottom sediments of the Lazarev Sea. 124 records from Total foraminifera counts of multinet M21/1_MSN620. 204 records from Abundance of organic-walled dinoflagellate cysts of sediment core GeoB1710-3. 11 records from Microzooplankton abundance and biomass at station TT050_21-13. 17 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/321-1. 16 records from Nannofossil abundance of Hole 24-235. 23 records from 2. Aspacher GEO-Tag der Artenvielfalt. 181 records from (Table 3) Range chart of calcareous nannofossils in ODP Hole 122-763B. 563063 records from Danish Mycological Society, fungal records database. 2 records from Radiolaria assemblage in sediment core GIK23400-3. 25969 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 2 records from Microzooplankton abundance and biomass at station TT050_15-3. 150 records from Psocodea (Mallophaga) collection of National Museum of Nature and Science. 21 records from Vogelwelt im Europa-Rosarium. 3394 records from Insect (SMNH-IN). 5056 records from IBF Monitoring of Lichens. 282 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 23 records from (Table 4) Relative abundance of the major nannofossil groups in the Lower Cretaceous of ODP Hole 113-693A. 10 records from (Table 3) Minerals and components of sediments from DSDP Site 94-609_Site, North Atlantic. 1763 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part III. 11333 records from Colección de referencia de vectores de Leishmania spp (causante de Leshmaniasis cutánea localizada) de la Península de Yucatán y un estudio preliminar en un área endémica de Quintana Roo. UADY_SNIB. 3 records from Akita Prefectural Museum＋Echiurans Specimens of Akita Prefectural Museum. 1 records from Description of lithologic section units of IODP Hole 325-M0052C. 103178 records from MfN - Heteroptera Collection. 1131 records from (Appendix A1) Abundances of planktonic and benthic foraminifera in the Turonian to Coniacian sediments of ODP Site 207-1259. 338 records from ConDidact Citizen Science Surveys - Snails 2012. 3477 records from Aves laguna El Tinije. 7 records from Analyses of the recent components of sediment core PS1219-1. 16 records from Occurrence of mammalia relicts at site Pestera lui Climente I. 23 records from Oligosarcus perdido (Characiformes, Characidae), a new species of freshwater fish from Serra da Bodoquena, upper Rio Paraguai basin, Brazil.. 2087 records from Range table from planktonic foraminifers in ODP Hole 144-871A. 4021 records from (Figure 7) Distribution of benthic foraminifers in the Oligocene to upper Miocene DSDP of Hole 71-513A. 4 records from Fossil (SMNH-FO). 1 records from Celaeno coccinea. 30625 records from Kochi Prefectural Makino Botanical Garden. 3695 records from Distribution of planktic foraminifera in ODP Site 202-1240 samples. 1 records from Zetes pilosus. 122 records from A contribution to the study of the Lower Volga center of scarab beetle diversity in Russia: checklist of the tribe Aphodiini (Coleoptera, Scarabaeidae) of Dosang environs. 264 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Picidae. 4 records from Zwei neue Arten der Oribatiden-Gattung Nanhermannia. 4318 records from Diptera Collection of Museum and Institute of Zoology PAS. 10000 records from National Lesser Horseshoe Bat Database. 140 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 120 records from Birdrace-The_early-Birds-Minden/Lübbecke. 63872 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 459 records from Colección de Entomología - Coleoptera - Chrysomeloidea. 2011 records from Local BioBlitz Challenge 2013. 11 records from Pollen profile from sediment core AV14_K2-4. 92 records from (Appendix) Diversity indices of benthic foraminiferal fauna of DSDP Hole 48-401. 11762 records from Chrysomelidae of the Carpathians. 7 records from Pseudochromis lugubris and P. tonozukai, two new dottyback fish species from the Indo-Australian Archipelago (Perciformes: Pseudochromidae: Pseudochrominae).. 22167 records from Natural History Museum Maastricht (NL) - Herbarium. 807 records from Reunion_Coffea. 2318 records from Fundación Miguel Lillo - Colección Ictiológica. 50 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña noviembre 2006. 66722 records from SANT herbarium vascular plants collection. 14 records from Plasm bearing foraminifera counts from multinet M31/2_MSN893. 56 records from Total foraminifera counts of multinet M21/5_MSN741. 3 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/321-1. 265 records from Luderbusch. 2 records from Nannofossil abundance of Hole 1-5. 81832 records from Herbaria of the University and ETH Zürich. 1158 records from Bulk components and planktonic foraminifera of sediment core GeoB7139-2. 362 records from (Table A.05) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (100-150 µm). 1083 records from Diversidad de Mariposas en la Reserva Natural El Romeral. 52 records from CIM Specimens. 1109 records from Gloucestershire Centre for Environmental Records - Gloucestershire BAP Priority Species - Water voles. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 146 records from Total foraminifera counts from multinet M31/2_MSN891. 1984 records from Planktic foraminiferal species counts in GeoB1117-2. 486 records from Dinoflagellates of sediment core GeoB1523-1. 9 records from Microzooplankton abundance and biomass at station TT043_2-1. 3 records from Sarcodine counts and carbon biomass at station TT007_7-CTD76. 2 records from Nannofossil abundance of Hole 3-20C. 407 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Buchaugraben in the Lower Inn Valley area. 155 records from Total foraminifera counts of multinet M10/2_MSN231. 157 records from Total foraminifera counts of multinet M21/6_MSN787. 139 records from Total foraminifera counts of multinet M42/3_MSN1364. 64 records from Lissarca notorcadensis. 11737 records from (Appendix II) Planktonic foraminiferal biostratigraphy of ODP Site 113-690. 328 records from Abundance of calcareous dinoflagellates of sediment core GeoB1214-1. 75 records from Abundance of microzooplankton measured on water bottle samples during POLARSTERN cruise ANT-X/6. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_10-CTD121. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 46 records from Phytoplankton abundance at bottle station A9/5. 160 records from (Table 1b) Relative percent abundance of planktic foraminiferal species at DSDP Site 77-536, Late Cretaceous. 1 records from FTEA. 47 records from Nannofossil abundance of Hole 64-479. 5 records from Nannofossil abundance of Hole 34-320A. 2 records from Nannofossil abundance of Hole 20-199. 14 records from Nannofossil abundance of Hole 94-611A. 145 records from Ostracoda abundance in DSDP Leg 87 holes. 19 records from Meiofauna abundance in sediment core 13200-001. 254 records from Grünes Germersheim. 1000 records from Plant (NHMK-PL). 94 records from Collection Bryozoa - ZMB. 38 records from Pollen profile ADR353. 252944 records from University of Florida Invertebrate Paleontology. 39650 records from (Table T1) Miocene planktonic foraminiferal stratigraphy of ODP Hole 184-1148A. 22 records from Bayerische Donau - Riedlingen. 132 records from Sukzession Industriebrache. 8551 records from Insect (ENHM-IN). 84 records from Taxonomic revision of the Neotropical Myrmicinae ant genus Blepharidatta Wheeler. 4317 records from Flora del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 7 records from Analyses of the recent components of sediment core PS1402-2. 18 records from Occurrence of mammalia relicts at site Steinheim an der Murr. 278 records from Planktic foraminifera abundance of Hole 39-354. 220 records from Foraminifera abundance of Hole 57-440. 654 records from Benthic foraminifera abundance of Hole 56-435. 285 records from (Table 4) Planktic foraminiferal abundance in Oligocene to Early Miocene sediments of ODP Hole 177-1090E on the Agulhas Ridge, South Atlantic. 11 records from (Table 5) Distribution of Nuttallides umbonifer and zonal age assignments of Eocene to Oligocene sediments of DSDP Hole 48-400A in the Bay of Biscay. 51 records from University of Amsterdam (NL) - Páramo Vegetation Research, Bordoncillo - Nariño, Colombia. 41 records from (Table 3a) Distribution of planktonic foraminiferal tests in sediments from Core NKA-37T. 153 records from (Table 2b) Relative abundance of planktonic foraminiferas in samples of surface sediments and in sediments accumulated about 18 ky ago from typical cores in the area of the Benguela upwelling. 5323 records from Anfibios y reptiles del estado de Nuevo León. 125272 records from Atlantic Reference Centre (OBIS Canada). 35020 records from Marine and Coastal Management - Demersal Surveys (years 2001-2005) (AfrOBIS). 16600 records from Fish Specimens of Museum of Tokushima Prefectural Museum, Japan. 177 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 8 records from Planktic foraminifera abundance of Hole 29-278A. 5 records from Dinoflagellates, pollen and spore abundance of Hole 29-280A. 9614 records from University of British Columbia Botanical Garden Collections (UBCBG). 2 records from Hildener Heide - Spörkelnbruch (Haan). 2794 records from Diversidad bentónica de la laguna Celestún, Yucatán. 6 records from Description of lithologic section units of IODP Hole 325-M0054B. 54 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 6 records from S
Keywords: GBIF; biodiversity; species occurrences